Background ion effects on the remediation of heavy metal-contaminated acid mine runoff using permeable reactive barriers: Mechanisms and field application - Wei Deng; Pingfeng Fu; Boyu Song; Wentao Hu; Siqi Zhang; Yunyun Li; Xiaofei Wang; Yuliang Zhang; Zeen Yu (Minerals Engineering, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Adsorption behaviour of tetracycline on fresh and aged Zn-modified biochar in the presence of copper: Insights into the synergistic effect and mechanism - Hua Deng; Song Lei; Shujia Chen; Xiaotong Zhou; Jiahui Fu; Pan Chen; Lening Hu; Anyu Li (Biomass and Bioenergy, 2026)

The characteristics of environmental parameters and cloud-to-ground lightning of thunderstorm cells in eight regions of South and Inland Plateau in China - Jie Deng; Fengxia Guo; Ke Chen; Qingyuan Wang; Miao He; Hanghang Fu; Yutan Chen (Atmospheric Research, 2026)

Autologous guided bone regeneration: a comprehensive narrative review - Zhi-Hao Yu; Xiang-Yi Deng; Zhi-Qiang Fan; Bao-Fu Yu (Molecular Biology Reports, 2026)

Investigation on optimization of hydrogen fuel cell ejector based on five-level spatially rotatable orthogonal test model - Yue Deng; Baiping He; Chao Li; Yaorui Shen; Boquan Qin; Jianqin Fu (Fuel, 2026)

Decoupling polarization losses in PEMFCs: A quadratic reduced-order optimization approach - Yaorui Shen; Baiping He; Hao Zhu; Yue Deng; Chao Li; Jianqin Fu (Fuel, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Time-dependent stiffness degradation of corroded stud connectors in steel-concrete composite bridges with typical defects - Jiancheng Gu; Chen Li; Mengxin Xue; Wenqin Deng; Yuguang Fu; Xinhao He (Engineering Structures, 2026)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Magnetite-assisted hydrothermal upgrading of polyvinyl chloride into an efficient heterogeneous Fenton catalyst - Ziyi Ding; Qingze Chen; Haoyang Fu; Fangxin Deng; Yanping Zhu; Yunfei Xi; Runliang Zhu (Journal of Environmental Chemical Engineering, 2026)

Comparative evaluation of hydroxylamine, sulfite, and ascorbate for low-micromolar Cu(II)-mediated bacterial inactivation in copper-containing wastewater contexts: Performance, redox behavior, and post-treatment toxicity - Jiali Peng; Junwei Yao; Chenye Fu; Qingqing Hao; Jingxingyu Wu; Yanyu Huang; Youheng Zhang; Shihuai Deng; Xiaohui Lu (Journal of Environmental Chemical Engineering, 2026)

Boosting domestic wastewater treatment with quorum signal-augmented heterotrophic nitrification-aerobic denitrification bacterial-algal aerobic granular sludge - Qian Zhang; Bixiang Nie; Chenxi Yang; Fu Wei; Lin Deng; Zheng Chen; Siyu Hua (Journal of Environmental Sciences, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Bacterial dehalogenases for organohalide and organofluorine remediation: Mechanistic insights, evidence gaps, and future relevance to GenX treatment - Derrick Boateng Kontoh; Dongyang Deng; He Fu; Mehdi Lamssalli (Chemosphere, 2026)

Multiomics analysis of the tolerance thresholds and decline mechanisms under sequential cumulative PE-MPs exposure in a novel HN-AD bacteria-Chlorella system treating synthetic wastewater - Qian Zhang; Lin Deng; Bixiang Nie; Fu Wei; Zheng Chen; Siyu Hua; Xiaozhuo Li; Chenhui Zhang; Yuyang Zhang; Quanli Chen (Process Safety and Environmental Protection, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Multifunctional dipole molecules-stabilized buried interface for high-performance air-processed regular perovskite solar cells with minimized energy losses - Kun Luo; Lu Deng; Ziyuan Liu; Xuxia Shai; Meirong Fu; Yue Yu; Xinxing Liu; Xingyu Gao; Dongmei He; Jiajia Zhang; Jiangzhao Chen (Chemical Engineering Journal, 2026)

Simultaneous interlayer expansion and surface ion-conductive coating for high-rate graphite anodes - Liming Zhang; Gang Chen; Zhihu Wang; Changming Qu; Longfei Li; Chengyu Fu; Wenwen Deng; Baozhang Li; Yi Sun; Jia-Wei Wang; Hongfa Xiang; Xuyong Feng (Chemical Engineering Journal, 2026)

Persistent regional hot-dry extremes identified by a novel cascading compound index and their possible association with ENSO transitions - Qimin Deng; Louise J. Slater; Christian L. E. Franzke; Yixuan Guo; Wuke Wang; Zuntao Fu; Boen Zhang; Sheng Wu (Climate Dynamics, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Intelligent water environment diagnosis and treatment center: A machine learning framework for automated surface water pollution management - Xinyang Zhang; Dijun Fu; Ruohong Li; Kewen Li; Xinzhe Zhu; Chuanhan Chen; Huanzhong Deng; Lianpeng Sun (Water Research, 2026)

Large language model-driven decision-making for single-atom Fenton-like catalysts toward wastewater treatment - Haoyang Fu; Qingze Chen; Chenliu Tang; Zhongyi Deng; Jingxiang Ng; Junbo Niu; Runliang Zhu; Shuzhou Li (Water Research, 2026)

A physics-informed data-driven approach for long-term settlement of embankment widening - Boyang Xia; Meng Wei; Gang Zheng; Haizuo Zhou; Weichao Liu; Yongfeng Deng; Jun Xiong; Wei Zeng; Ziying Fu (Transportation Geotechnics, 2026)

Experimental and numerical study of prefabricated bridge columns with UHPC-core socket connection - Jundong Fu; Zheng Lu; Tong Deng; Dianchao Wang; Shui Wan; Xilin Lu (Soil Dynamics and Earthquake Engineering, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Rhamnolipid@Ag bio-nanofluids for enhanced oil recovery: Multiscale experimental and molecular mechanism elucidation - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Journal of Cleaner Production, 2026)

Decoupling of soil reactive oxidized and reduced nitrogen gas emissions across a coastal wetland reclamation chronosequence - Wentao Qiao; Lingling Deng; Ruhai Wang; Zehua Fu; Guoyu Yin; Dianming Wu (Journal of Environmental Management, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

An optimized inflow turbulence generator for LES of wind effects on high-rise buildings using MINSRFG method - Yangxue Wang; Shidi Wang; Ting Deng; Jiyang Fu; Ching Tai Ng (Engineering Structures, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

Mechanism of synergistic removal of refractory organic matter and ammonia nitrogen in pharmaceutical wastewater tailwater by iron‑carbon micro-electrolysis enhanced biological system - Fu Wei; Bixiang Nie; Lin Deng; Zheng Chen; Siyu Hua; Qian Zhang (Chemical Engineering Journal, 2026)

Mechanistic insights into nitrogen-doping-assisted biomass-derived graphitization carbon catalyzed by iron nitrate - Guangda Fu; Zhengshuai Sun; Baojun Yi; Jiaqi Deng; Xing Wu; Dongyi Kong (Biomass and Bioenergy, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Identification of suitable habitats for the six-spotted mite on rubber trees using multi-source data and MaxEnt modeling - Yanan You; Huichun Ye; Donghua Wang; Chaojia Nie; Jingjing Wang; Bingsun Wu; Fengzheng Cai; Jiajian Deng; Lixia Shen; Fu Wen (Experimental and Applied Acarology, 2026)

Non-fickian CO2CH4 transport in carbonate composite cores analyzed with fractional-order model and in-situ NMR characterization - Miao Zhang; Lianlin Deng; Bo Ning; Jianlin Guo; He Yuan; Ninghai Fu; Luis F. Ayala (Advances in Water Resources, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Regional-scale prediction and assessment of soil organic matter content in the Yuanmou Dry-Hot Valley, Southwest China, using satellite-derived phenological time series and deep learning - Dengdeng Ding; Jida Yang; Sihe Deng; Hongye Zhu; Zhengbo Ma; Chengxiu Fu; Junlang Deng; Dingyun Zhao; Zhen Long; Xiaoyan Wang; Peiwen Yang; Qibin Chen; et al. (Environmental Monitoring and Assessment, 2026)

Intestinal barrier heterogeneity mediates intestinal health advantage of baling Tieshan organic bighead carp - Zhen Huang; Chigang Huang; Yizhen Wang; Shuxia Yao; Deng Pan; Xueru Qian; Fangyuan Peng; Lingwei Tang; Jinghui Liu; Wen Fu; Liangyue Peng; Yamei Xiao; et al. (Aquaculture, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Study on the along-wind response and aerodynamic mechanism of supertall buildings under setback tapering and rotation designs - Yangxue Wang; Ting Deng; Ching Tai Ng; Jiyang Fu (Engineering Structures, 2026)

A coordinated scheduling approach with electricity peak shaving capability for integrated office Building-EV system - Jiesheng Yu; Yongming Zhang; Zhe Yan; Hai Ye; Weidong Fu; Hua Deng; Zhongyang Qian (Energy and Buildings, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

Nonlinear dynamic analytical model of multi-span transmission line-insulator systems following entire-span ice shedding - Dahai Wang; Yuchen Fu; Yaqi Zhao; Zhanhao Deng; Zenghao Huang (Cold Regions Science and Technology, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Local mitigation, regional leakage? Climate effects of sustainable development policy in China’s resource-based cities - Liyun Wang; Hongyu Cai; Xu Fu; Guoying Deng (Urban Climate, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

14-3-3σ alleviates UVB-induced epidermal oxidative stress through the pentose phosphate pathway promotion - Xuyi Deng; Zhengzheng Fu; Xinli Niu; Peiqi Lian; Hui Liu; Yinghui Wang; Fangming Li; Meijuan Zhou (Journal of Photochemistry and Photobiology B: Biology, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Optimizing HN-AD bacteria-Chlorella symbiotic system via QS molecules for biogas slurry treatment - Qian Zhang; Fu Wei; Shumin Qin; Bixiang Nie; Lin Deng; Zheng Chen; Siyu Hua (Journal of Environmental Chemical Engineering, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Antibacterial properties of sweeping-frequency ultrasonic modified xanthan gum@ZnO composite film and application in grape preservation - Lei Zhang; Haiyang Zhang; Shanshan Zhou; Yan Shen; Binglin Fu; Jilong Deng; Hafida Wahia; Xiaojie Yu; Haile Ma; Cunshan Zhou (Food Chemistry, 2026)

Corrigendum to “Enhancement of composite film properties by sweeping-frequency ultrasound modified xanthan gum and nano ZnO: structural and functional characterization” [Food Hydrocolloids, 175, (June 2026), 112449] - Lei Zhang; Haiyang Zhang; Shanshan Zhou; Binglin Fu; Jilong Deng; Yan Shen; Hafida Wahia; Xiaojie Yu; Haile Ma; Cunshan Zhou (Food Hydrocolloids, 2026)

Enhancement of composite film properties by sweeping-frequency ultrasound modified xanthan gum and nano ZnO: structural and functional characterization - Lei Zhang; Haiyang Zhang; Shanshan Zhou; Binglin Fu; Jilong Deng; Yan Shen; Hafida Wahia; Xiaojie Yu; Haile Ma; Cunshan Zhou (Food Hydrocolloids, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Cyanofunctionalized A-shaped non-conjugated nanopolymer as a hole-transporting material for blue perovskite light-emitting diodes - Tonglin Yang; Weihao Zhang; Yifan Wang; Fangju Tao; Fu Deng; Chunxiao Zhong; Ying Wei; Lihui Liu; Linghai Xie (Chemical Engineering Journal, 2026)

Cyclophosphamide-induced iron homeostasis imbalance triggers ovarian toxicity through ferroptosis of ovarian granulosa cells in a mitophagy crosstalk manner - Bo Xu; Xiaoqiang Luo; Tengjiao He; Yu Deng; Yitong Shang; Hang Han; Xufeng Fu (Chemico-Biological Interactions, 2026)

Study on the synergistic efficacy and mechanism of CD24 silencing combined with trastuzumab in HER2-positive breast cancer - Yi Lu; Xinglu Zhou; Yue Gao; Zi Zhu; Bao Deng; Wubin Lv; Zhenkun Fu; He Ding; Lei Zhong (Journal of Molecular Histology, 2026)

Single-cell transcriptomics and multimodal molecular profiling revealed the oncogenesis and tumor microenvironment of cardiac myxoma - Xinyi Yu; Yibo Shi; Mingjie Xie; Kailong Deng; Zean Fu; Shuang Hao; Yu Pei; Zhenxing Liang; Longhui Guo; Jia Li; Jingchao Zhang; Xinwei Han (Science China Life Sciences, 2026)

Effect of Dip Angle on Permeability of Hydraulic Rough Fractures During Shale Reservoir Depletion and Shut-in Recovery: insights from True Triaxial Loading–Unloading Tests - Jiaxin Zhu; Tianyu Chen; Dawei Deng; Yu Wang; Xueyan Jiang; Zhiguo Wang; Yunlong Fu; Jiyuan Lu; Hongming Zhang; Zhejun Pan (Rock Mechanics and Rock Engineering, 2026)

Development and application of LED-based UV–Vis spectrophotometer for in-situ monitoring in industrial wastewater discharge networks: Pattern classification, anomaly identification, and targeted optimization - Zhehua Xue; Jinxin Chen; Chicheng Deng; Jiaqing Mu; Yuewei Tang; Chenyu Chen; Zhenzhou Zhang; Fangze Shang; Hao Fu; Wentao Li (Journal of Water Process Engineering, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Dense planting coupled with optimized irrigation improves rice yield while reducing Cd level in rice grain and CH4 emission from field - Zhiwei Tang; Xin Zhang; Aixing Deng; Jun Zhang; Zhenwei Song; Xiangcheng Zhu; Jin Chen; Min Xie; Fu Chen; Weijian Zhang (Field Crops Research, 2026)

Development and hypermobility of the Basu rock avalanche in the Nu River ophiolitic mélange, southeastern Tibetan Plateau - Yunjian Gao; Jianhui Deng; Siyuan Zhao; C.F. Lee; Xin Yao; Fuchu Dai; Stuart Lane; Yongbo Tie; Kaiyu Ren; Fei Wang; Ziguo Fu (Engineering Geology, 2026)

Network structural-functional mismatch dominates the cascading processes of flood regulation service flows - Chuxiong Deng; Jiawen Fu; Guangjie Zhang; Yaojun Liu; Sihan Li (Ecological Engineering, 2026)

Three-phase interface modulation strategy for SERS detection of pathogenic bacteria in complexed media - Sensen Zhou; Ruiqi Peng; Boyan Zhao; Yong Wang; Chen Fu; Wei Deng; Dan Li (Chemical Engineering Journal, 2026)

How Increasingly Frequent Drought-Flood Abrupt Alternation Events Affect Reservoir Operation? - Yifan Huang; Jianyu Fu; Xuejin Tan; Zhihong Deng; Haibo Peng; Wenzhi Zhang; Bingjun Liu (Water Resources Management, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Evaluating the performance of coastal virtual stations from different combinations of altimetry missions - Fukai Peng; Zhong He; Xiaoli Deng; Ole Baltazar Andersen; Dapeng Mu; Yunzhong Shen; Yanguang Fu; Xiao Cheng (Advances in Space Research, 2026)

Comprehensive Comparison on Potentially Toxic Elements Between Sandstorm PM2.5 and Haze PM2.5 - Jiaojiao Xie; Yixian Long; Songyao Liu; Yiran Fu; Chun-Gang Yuan; Mingyu Li; Shuang Deng (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Circular economy of Castanea henryi : high-value utilization and processing technologies advances - Zhi-hui Deng; Bin Yuan; Yuan-yuan Lu; Xiao-ming Tian; De-fang Niu; Feng Zou; Xiao-ming Fan; De-yi Yuan; Fu-liang Hu (Critical Reviews in Food Science and Nutrition, 2026)

Experimental investigation on vortex-induced vibration of a free-hanging flexible riser under different bottom clump weights - Zhibo Niu; Shixiao Fu; Xuepeng Fu; Xueqin Liu; Mengmeng Zhang; Jiawei Shen; Pengqian Deng (Ocean Engineering, 2026)

Supercooled sodium acetate trihydrate-erythritol eutectic phase change composites for all-weather photovoltaic thermal management - Yizhe Liu; Yangzhe Xu; Ziyu Tian; Minling Liu; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Journal of Cleaner Production, 2026)

Enhanced pollutant removal via polybutylene succinate-based microbial-agent biofilm process: Optimizing heterotrophic nitrification–aerobic denitrification technology for low-carbon wastewater treatment - Qian Zhang; Zheng Chen; Kun Long; Bixiang Nie; Fu Wei; Lin Deng; Siyu Hua (Journal of Environmental Chemical Engineering, 2026)

Effect of oxidation degree on high-temperature rheological properties and extruded soybean protein - Liwei Fu; Benu Adhikari; Qian Deng; Zhiyong He; Maomao Zeng; Jie Chen; Zhaojun Wang (Food Hydrocolloids, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

NbB2-Fe self-cascading glucose oxidase-like and peroxidase-like nanoparticles - Sihua Deng; Jiangling Wu; Menglin Li; Yaqing Chen; Yifan Han; Qi Zhou; WenSheng Fu (Chemical Engineering Journal, 2026)

A Real-World Disproportionality Analysis of Drug-Induced Heart Failure: Integrating FAERS Database and AHA Statement - Da Li; Yidan Dong; Lei Yao; Xiaozhe Chen; Yunfeng Li; Xiaohong Deng; Jianhua Li; Mingzhu Wang; Deyu Fu (Cardiovascular Toxicology, 2026)

How does recreation involvement in urban parks promote restorative effects? - Erkang Fu; Lin Li; Jiawen Zhou; Li Deng; Mingxuan Pu; Peilin Qu; Yijun Xu; Xi Li (Urban Forestry & Urban Greening, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Synergistic optimization of computing-power-cooling-heat multi-energy flow: Integrating flexible data centers and district heating networks - Chao Fu; Kai Zhang; Chuanzi Deng; Qingfei Shen; Tong Wu (Journal of Cleaner Production, 2026)

Effect of molecular weight of carboxymethyl chitosan on the properties of modified pea protein isolate-carboxymethyl chitosan complexes and its potential as stabilizer for high internal phase emulsions - Mianzhang Zhang; Hongliang Li; Shulin Deng; Shiyi Ou; Fu Liu; Jie Zheng (Food Hydrocolloids, 2026)

Dual MOFs-Derived CdS/In2S3 heterojunction photocatalyst for fast and efficient reduction of Cr(VI) - Hong Wu; Zhuoqi Liu; Tianrong Xiong; Xingyan Liu; Ying Chen; Min Fu; Yue Deng; Yongcheng Feng; Yuyu Fang; Bowen Lei; Youzhou He (Environmental Research, 2026)

Synergistic effects of high temperature and hypoxia on energy metabolism and physiological homeostasis in the Chinese mitten crab (Eriocheir sinensis) - Cong Zhang; Dunqian Deng; Huixia Feng; Su Jiang; Zihao Song; Kai Zhang; Longlong Fu; Shaowu Yin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Hydrated salt composites with binary carbon networks and laser-treated hydrophobic surfaces for multifunctional outdoor building thermal management - Yizhe Liu; Weizheng Cheng; Yangzhe Xu; Modi Jiang; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2026)

Use of stable nitrogen isotopes in atmospheric aerosol research - Jingqi Bai; Libin Wu; Qingzi Zhao; Ke Xin; Wei Hu; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Optimizing environmental surveillance for early detection of zoonotic pathogens via fecal shedding modeling - Xin Du; Zhiqiang Deng; Yuqing Long; Fenglan He; Chunlong Zhu; Chun Han; Hui Li; Songzhe Fu (Water Research, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Inhibitory effects and mechanisms of dichloromethane on a biological contact oxidation process for chemical wastewater treatment - Bixiang Nie; Lang Jiang; Fu Wei; Lin Deng; Zheng Chen; Siyu Hua; Qian Zhang (Process Safety and Environmental Protection, 2026)

Steel slag-based reactive media with varied Fe/Ca ratios in permeable reactive barrier for As, Sb and Pb co-contaminated acid mine runoff remediation: Efficiency and mechanisms - Wei Deng; Pingfeng Fu; Wentao Hu; Siqi Zhang; Yunyun Li; Xiaofei Wang; Yuliang Zhang; Zeen Yu (Journal of Environmental Chemical Engineering, 2026)

Ammonia-hydrogen blends combustion in turbulent high temperature co-flow - Meng Ji; Zhijun Wu; Oscar Vento; Quanbo Shang; Chaoqun Hu; Alessandro Ferrari; Lezhong Fu; Jun Deng; Liguang Li (Fuel, 2026)

Scalable production of antioxidant ‘sandwich’ films from all-natural composites for inhibiting fruit browning - Jie Deng; Hao Fu; Xinhong Li; Jieping Liu; Yuancheng Zhang; Wenxin Zhao; Baofeng Lin (Food Chemistry, 2026)

Economic benefits of carbon source selection for polyphosphate-accumulating organisms in enhanced biological phosphorus removal - Jing Yuan; Liping Chen; Xiaojing Xie; Hang Chen; Xiaodong Du; Acong Chen; Haixin Zheng; Fu Huang; Sijia Ji; Zemin Li; Xianghui Liu; Zhiyi Deng; et al. (Environmental Research, 2026)

Tidal intensity and suspended sediment concentration drive microplastic distribution in the Pearl River Estuary: Insights from remote sensing retrieval - Yutao Fu; Hua Deng; Wenping Gong; Jian He; Lixue Zhang; Yugen Ni (Environmental Pollution, 2026)

Dynamic response reconstruction of high-rise buildings under hazards using a Pyramid-LSTM-Attention network - Haoran Pan; Fan Jiang; Jia Guo; Ting Deng; Jiyang Fu (Engineering Structures, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Combined aperture widening and strong polarization in Li+-exchanged mordenite for efficient direct air capture of CO2 - Zhifu Liu; Guanghui Shi; Shuzhuang Sun; Yong Wang; Jingyue Shang; Songbai Hu; Wenkang Deng; Chuhan Fu; Chenghao Liu; Xiao Wang; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

From bioprocess to market: Optimizing medium-chain carboxylate extraction for application readiness - Yiran Zhang; Aijie Wang; Yilu Sun; Xuening Zhang; Jianfeng Liu; Wen Wang; Cong Huang; Shaoping Fu; Honggang Deng; Yongping Shan; Jiadong Yu; Xufeng Yuan; et al. (Bioresource Technology, 2026)

Study of the combustion behavior of wheat straw using TG–DSC under multiple heating rates - Jialiu Lei; Yucheng Zhang; Jingtao Zhou; Shiru Deng; Yongjun Fu (Biomass and Bioenergy, 2026)

Spatiotemporal Variation Analysis of Yangtze River Basin Water Quality in Chong Qing, China During 2021–2023 Based on Improved Water Quality Assessment - Libo Ran; Xing Wei; Yulin Zhou; Qingmei Zhang; Yanan Fu; Zikan Deng (Water, Air, & Soil Pollution, 2026)

Stabilization stage dissolved oxygen and contact-stabilization time ratio synergistically govern quorum sensing-mediated sludge bulking in the high-rate contact-stabilization process - Zhongqi Jiang; Shan Qiu; Mengxuan Deng; Mengqi Fu; Zikun Jin; Mu Yuan; Wei Zhang; Chuandong Wu (Water Research, 2026)

Corrigendum to “Chlorpyrifos induces placental oxidative stress and barrier dysfunction by mediating mitochondrial apoptosis via ERK/MAPK signaling pathway: In vitro and in vivo studies” [Sci. Total Environ. 903 (2023), 166449] - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2026)

The CsWRKY3–CsHB7 transcriptional cascade promotes temperature-responsive peel pigmentation via CsCCD4b-mediated β-citraurin biosynthesis in citrus - Ranran Wei; Ang Fu; Yu Fang; Quan Sun; Zhijing Mo; Pengtao Yue; Ying Liang; Zongzhou Xie; Lijun Chai; Junli Ye; Xiuxin Deng (Molecular Plant, 2026)

Understanding interaction between flow field vortex and combustion of an evaporating tube-type annular combustor - Yanzhao An; Yuzhang Wang; Shicheng Shen; Chuang Chen; Yiqiang Pei; Zhiteng Zhu; Xueqing Fu; Wei Zhu; Yan Zhang; Xiaoyu Zhang; Wei Deng (Fuel, 2026)

Characterizing the millimeter-scale combustion front in porous media - Zeyang Song; Chongbao Zhao; Yaohan Wang; Jiacheng Fu; Jun Deng (Fuel, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Void ratio-dependent soil-water characteristic curve and hydraulic conductivity of unsaturated loess considering the film flow under high suction range - Yukai Fu; Ziran Zhang; He Liu; Feng Zhang; Tonglu Li; Longsheng Deng (Engineering Geology, 2026)

Two-Temperature Thermoporoelastic Modeling of Experimental Data for Wave Propagation in Glycerin-Saturated Tight Sandstones - Nianqi Li; Li-Yun Fu; José M. Carcione; Wubing Deng (Rock Mechanics and Rock Engineering, 2026)

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

Pore Structure Evolution in Marine Sands Under Laterally Constrained Axial Loading - Xia-Tao Zhang; Cheng-Liang Ji; Le-Le Liu; Hui-Long Ma; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Installation in sand is sensitive to its evolving pore structure, yet design models rarely update permeability for real-time fabric changes. This study tracks the stress-dependent pore size distribution of coarse sand under laterally constrained compression using high-resolution X-ray nano-CT. Scans taken at six axial stress levels show that the distribution shifts toward smaller radii while keeping its log-normal shape. A single shifting factor, defined as the current median radius normalized by the initial value, captures this translation. The factor decays with axial stress according to a power law, and the exponent as well as the reference pressure are calibrated from void ratio data. The resulting closed-form expression links mean effective stress to pore radius statistics without extra fitting once the compressibility constants are known. This quantitative relation between effective stress and pore size distribution has great potential to be embedded into coupled hydro-mechanical solvers, enabling engineers to refresh hydraulic permeability at every computation step, improving predictions of excess pore pressure and soil resistance during suction anchor penetration for floating wind foundations.

Investigation of Pullout Capacity Characteristics of Suction Anchors Under Inclined Loads in Layered Soil - Cheng-Liang Ji; Xia-Tao Zhang; Hao-Yu Wang; Le-Le Liu; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Suction anchors are widely used in marine engineering because of their easy installation, cost-effectiveness, and excellent load-bearing capacity. However, existing research on their bearing capacity has primarily focused on homogeneous soils, which fails to adequately reflect the actual bearing capacity of layered seabed soils. Therefore, this study conducted a series of numerical simulations to investigate the pullout bearing capacity of suction anchors subjected to inclined loads in upper-stiff–lower-soft layered clay. By considering the clay strength (Sum/kD) and soil layer thickness ratio (Th/L, Tc/L), this study systematically explores the influence of the optimal centerline loading depth (Zcl,opt), uniaxial ultimate bearing capacity (Hult and Vult), and the VH failure envelope of suction anchors. The results indicate that the layer thickness ratio Th/L of lightly overconsolidated clay (LOC) is the key factor influencing the Zcl,opt and ultimate bearing capacity Hult and Vult. An increase in Th/L significantly enhances the pullout resistance of suction anchors, which primarily results from the combined enhancement effect of lateral friction resistance and end resistance at the anchor–soil interface. The layered clay has a distinct influence on the horizontal and vertical bearing capacities of suction anchors. Based on the results of parameter analysis, a conservative analytical expression for the lower bound of the VH failure envelope curve is further proposed. The research conclusions provide a theoretical basis and engineering practice guidance for the optimized design and safety assessment of suction anchors in layered soil.

Sewage surveillance revealed the emergence and prevalence of human rhinovirus and human parainfluenza virus in China based on their fecal shedding rates - Xin Du; Yao Deng; Hongxia Ming; Haifeng Li; Chunlong Zhu; Fenglan He; Songzhe Fu (Water Research, 2025)

Stratification and deposition pathways of microplastics in the abyssal sediments of the Philippine Sea - Hua Deng; Yutao Fu; Ming Su; Daohua Chen; Huiqiang Yao; Yufang Tan; Lixue Zhang; Jinlian Wang; Yinan Deng (Water Research, 2025)

Microbial abundance shapes latitudinal pattern of the greenhouse gas production potential in blue carbon ecosystems - Lingfang Ni; Chuancheng Fu; Gang Li; Kai Feng; Ye Deng; Jiaping Wu; Carlos M. Duarte; Yuan Li; Dongdong Zhang (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Evaluating quasi-elastic behavior in granular Materials: Insights from cyclic loading tests - Pingxin Xia; Qingqing Fu; Wen Deng; Xiaoshuang Li; Maosen Han; Tiande Wen (Soil Dynamics and Earthquake Engineering, 2025)

Comprehensive fatigue assessment in deep-sea enclosed cabins using optimized multi-dimensional weighting - Wei-lan An; Jing Chen; Jin-chi Fu; Zhao-xian Ren; Deng-kai Chen (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Analyzing multidimensional mismatches in the supply-demand of hydrological-related ecosystem services in humid regions - Guangjie Zhang; Chuxiong Deng; Yaojun Liu; Jiawen Fu (Journal of Hydrology, 2025)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Biochar-fertilizer synergy for manganese tailings remediation: A study for metal immobilization and ecosystem restoration - Dong Zhao; Shuyun Zhang; Yu Yang; Shunyun Ye; Jiahui Fu; Lening Hu; Anyu Li; Hua Deng (Journal of Cleaner Production, 2025)

Donor-acceptor structured boron-doped g-C3N4 photocatalysts for enhanced tetracycline degradation and H2O2 production - Xiangdong Chen; Meng Wang; Zhonghui Fu; Yiping Deng (Journal of Cleaner Production, 2025)

Early Miocene fossils from Shaoma, China, evidence Eurasia-North America ruminant exchange - Shi-Qi Wang; Tao Deng; Tingjiang Peng; Bian Wang; Qigao Jiangzuo; Jiao Fu; Danhui Sun; Luda Xing (Geobios, 2025)

A combination of ultrasound treatment and self-assembly with carboxymethyl chitosan-gallic acid conjugate on pea protein isolates: Effect on structure, functional and thermal stability properties - Mianzhang Zhang; Shulin Deng; Juanying Ou; Caihuang Huang; Fu Liu; Shiyi Ou; Jie Zheng (Food Chemistry, 2025)

Two isoforms of Rel gene involved in the immune regulation of pearl oyster Pinctada fucata martensii - Hongxi Chen; Guixuan Chen; Zhihao Chen; Xiaowen Lu; Shirong Fu; Weijiang Liao; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Green synthesis and functionalization of rice husk-derived SiO₂ nanoparticles for scale inhibition: A multiscale study combining experiments, molecular dynamics simulations, and quantum chemical calculations - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Chemical Engineering Journal, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Numerical investigation of the screen mesh effects on the heat transfer performance of wick structured heat pipe - Youyuan Fu; Da Chen; Yuxuan Cui; Shang Mao; Zilong Deng (Annals of Nuclear Energy, 2025)

The Increased Effect of Spring Leaf Unfolding on Autumn Senescence in the Northern and Southern Hemispheres - Dong Tang; Shubin Xie; Jie Peng; Ying Sun; Abraham Allan Degen; Yuan Sun; Jiali Luo; Zifan Li; Yaning Kuang; Lixue Wei; Weigang Hu; Longwei Dong; et al. (Global Ecology and Biogeography, 2025)
Aim To investigate the contributions of vegetation growth carryover (VGC, defined as the effect of present states of vegetation growth on subsequent phenophases) and climatic factors to plant phenology, particularly start‐of‐season (SOS) and end‐of‐season (EOS), and how these contributions have evolved globally over the past four decades. Location Global, with a focus on the Northern Hemisphere (NH) and Southern Hemisphere (SH). Time Period 1963–2015 for ground observations, 1982–2022 for satellite NDVI data, and 1982–2022 for climate data (temperature, precipitation, radiation, and potential evapotranspiration). Major Taxa Studied Global vegetation, without specifying individual species. Methods We analysed two sets of satellite‐derived NDVI data, ground‐based phenological observations, and long‐term climate data (temperature, precipitation, radiation, and potential evapotranspiration). Statistical models quantified the contributions of climatic factors and VGC to phenology trends. Results Globally, advanced SOS was driven primarily by increasing temperature and radiation, while delayed EOS was attributed to rising temperature and the carryover effect of spring vegetation growth (VGC SOS ). VGC SOS was the dominant driver of EOS in the SH, whereas temperature played a larger role in the NH. Over the past four decades, the contribution of VGC SOS to EOS has increased significantly on a global scale. However, the SH experienced pronounced “warming and drying” trends, which weakened the relative contribution of VGC SOS to EOS compared to climate‐driven delays. Main Conclusions VGC SOS plays a substantial role in shaping EOS in both hemispheres, with its importance increasing over time. These findings improve our understanding of vegetation dynamics and offer valuable insights for predicting vegetation growth and carbon sequestration under future global warming scenarios.

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Intensified rainfall overrides vegetation greening in driving erosion and carbon loss on the Tibetan Plateau - Rui Deng; Dongfeng Li; Yi Zhao; Desmond E. Walling; Panos Panagos; Pasquale Borrelli; Philippe Ciais; Yuefei Huang; Yuanyuan Bai; Sergey Chalov; Valentin N. Golosov; Xudong Fu; et al. (Science Bulletin, 2025)

Cross-scenario transfer learning for estimating mangrove nitrogen and phosphorus content from field hyperspectral data to SDGSAT-1 and Sentinel-2 images - Bolin Fu; Yan Wu; Li Zhang; Weiwei Sun; Yeqiao Wang; Tengfang Deng; Hongchang He; Keyue Huang (Remote Sensing of Environment, 2025)

Light absorption and molecular composition of brown carbon in Nanjing, China: Large contribution of biomass burning and secondary formation - Junjun Deng; Xinfeng Wang; Jialei Zhu; Wei Hu; Libin Wu; Pingqing Fu (Journal of Environmental Management, 2025)

Sustainable integrated synthesis of high-yield and high-purity lignin-derived carbon dots: Dual-functional fluorescence detection and efficient chromatographic separation of nitro-antibiotics - Yuanmin Gong; Dan Wang; Panpan Chen; Renyu Deng; Meiting Yan; Baian Ji; Lingling Liu; Xueping Tao; Zhining Xia; Qifeng Fu (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

Multi-component heterogeneous interface engineering and magnetic domain evolution for broadband electromagnetic wave attenuation - Yuhui Peng; Jiarong Liu; Zhaobo Feng; Jinbin Peng; Yangxiao Guo; Yue Zhang; Yanjun Fu; Chongbo Liu; Lianwen Deng (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Inhibitory effects of biological soil crusts on splash erosion across two contrasting lithologies in karst regions of Southwest China - Shiqin Zhang; Jingqin Shi; Lanhui Yang; Jingben Xu; Yongshi Tan; Yuanfeng Yang; Fang Wang; Zhiyong Fu; Hongsong Chen; Yusong Deng (CATENA, 2025)

Correction: The PGC-1α/SIRT3 pathway mediates the effect of DON on mitochondrial autophagy and liver injury in mice - Yihan Wang; Jiali Fu; Danni Zhou; Zhihua Ren; Junliang Deng (Mycotoxin Research, 2025)

Integrating remote sensing and mechanistic model for spatial evaluation of shelterbelt porosity and windbreak effectiveness in agricultural landscapes - Xing Zhang; Bolin Fu; Rongxin Deng; Ying Li; Jingwen Li; Jianwu Jiang; Jing Tang (Agricultural and Forest Meteorology, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Experimental study of rock-machine interaction responses in sandstone with distributed boreholes through TBM tunnelling test - Wei-Qiang Xie; Xiao-Li Liu; Xiao-Xiong Zhou; Nai-Fu Deng (Tunnelling and Underground Space Technology, 2025)

Reveal the structure of plants by X-ray imaging and biomedical beamline at SSRF - Guohao Du; Jianfeng Ji; Han Guo; Yanling Xue; Yanan Fu; Biao Deng; Honglan Xie; Tiqiao Xiao (Phytochemistry Letters, 2025)

Potential for hydroxamic acid modification via electronic effect: A case study of enhanced cassiterite flotation - Zhifeng Zhang; Yao Yu; Junhao Fu; Jian Cao; Chaozheng Deng; Wei Sun; Haisheng Han (Minerals Engineering, 2025)

Heavy metal exposure and cognitive impairment: An umbrella review of meta-analyses - Yueqing Song; Yantong Chen; Zhushan Fu; Yi Wen; Weiyue Zhao; Jia Li; Haocheng Wang; Yinke Du; Yu Deng (Journal of Hazardous Materials, 2025)

Biotransformation and toxicity attenuation of 2,6-Dichlorobenzoquinone in simulated human gastrointestinal conditions: Insights from a systematic in vitro study - Lili Zheng; Guolong Chen; Kuangtao Fu; Zhen Wang; Xinyue Yuan; Hongjie Sun; Wenjing Deng; Zeqiong Xu; Hongjun Lin; Huachang Hong (Journal of Hazardous Materials, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Freeze-thaw and dry-wet alternation regulate the impacts of Fe-C based passivator on soil heavy metals immobilization - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Environmental Chemical Engineering, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

Stepwise recovery of gallium (Ga), lithium (Li), and rare earth elements (REEs) from roasted coal gangue based on leaching kinetics differentiation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Kejia Ning; Biao Fu; Lin Ma; Xin Sun; Yuntao Kang; Mengting Hong; Guixia Fan; Xiahui Gui; Jiushuai Deng (Hydrometallurgy, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Investigation of wind load characteristics and structural responses in asymmetric linked twin-tower high-rise buildings - Yangxue Wang; Ting Deng; Jiyang Fu (Engineering Structures, 2025)

Machine learning-assisted biomass colorimetric dipsticks for portable clinical nephropathy diagnosis by using smart mobile terminal - Donglei Fu; Lin Ding; Bowen Zhang; Shuaibo Zhang; Junjie Deng; Ruyi Wei; Hua Shui; Xinghai Liu (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Self-powered drifting buoy for maritime anomaly traffic monitoring via electromagnetic-triboelectric coupling - Hanlin Zhou; Zhiqiang Yang; Zhi Cao; Junbo Wang; Hao Qian; Jizhong Deng; Yuxuan Zhou; Yingwei Zhao; Hailin Fu; Zhiyi Wu (Chemical Engineering Journal, 2025)

Active cellulose-based film with synergistic enhanced photothermal antibacterial effects by Fe-doped ZIF-8 and EGCG for efficient litchi preservation - Wenxin Zhao; Yuntong Liang; Yuancheng Zhang; Yongfu Deng; Hao Fu; Xu Yuan; Zhen Wang; Xiaohe Lu; Baofeng Lin (Chemical Engineering Journal, 2025)

Chalcone derivatives containing 1,2,4-triazole and pyridine moiety: design, synthesis, and antiviral activity - Hui Xin; Jiao Tian; Tianyu Deng; Qing Zhou; Yuhong Wang; Hong Fu; Haotao Pu; Wei Xue (Molecular Diversity, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Temporal trends of the disease burden of renal cell carcinoma from 1992 to 2019 in the US: a population-based analysis - Ruyan Chen; Tian Tang; Jianglong Han; Si Li; Wenmin Liu; Haiyu Deng; Tingting Jian; Zhenming Fu (Cancer Causes & Control, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Watershed runoff as a dominant pathway for mercury loading into a karst lake as unraveled by a novel mercury isotope and flux balance model - Hui Zhang; Xuewu Fu; Xian Wu; Qianwen Deng; Kaihui Tang; Leiming Zhang; Jonas Olof Sommar; Xinbin Feng (Water Research, 2025)

Biogeochemical controls on metal distribution and pedogenesis in tropical island soils - Chin Yik LIN; Peili DENG; Mohd Talha ANEES; Fu-Jun YUE; Su Shiung LAM; Hu DING; Elanni AFFANDI; Baba MUSTA (Pedosphere, 2025)

The red river fault zone and its deep structural characteristics revealed by high-resolution seismic data in the Yinggehai basin, South China sea - Tao Wu; Jianxiang Pei; Yongtao Fu; Dun Deng; Guanfei Chen; Tao Xu; Dingding Wang; Zhangguo Zhou; Wanyin Wang (Journal of Structural Geology, 2025)

Characterizing the capability of public DEMs for mapping global floodplain bathymetry - Yaling Lin; Chenyu Fan; Kai Liu; Lingyang Liu; Xinyuan Deng; Pengju Xu; Pengfei Zhan; Xuefei Fu; Chunqiao Song (Journal of Hydrology, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

The autoignition characteristics of oxygen-in-ammonia blending fuel turbulent jet flame into high temperature co-flow - Meng Ji; Zhijun Wu; Zhe Kang; Quanbo Shang; Guanyu Zhang; Chaoqun Hu; Lezhong Fu; Yang Yu; Jun Deng; Liguang Li (Fuel, 2025)

Integrating hotspots, trade-offs and bundles to reveal the spatial interactions among four water-related ecosystem services for systematic watershed management - Chuxiong Deng; Guangjie Zhang; Yaojun Liu; Yajing Gong; Jiawen Fu (Ecological Engineering, 2025)

Thorium-selective electrosorption with phosphorylated PANI/AC electrode - Chunyan Fu; Wenqi Du; Wangqiang Kuang; Yabin Huang; Bicheng Deng; Xiaojuan Liu; Youming Yang; Shengting Kuang; Wuping Liao (Chemical Engineering Journal, 2025)

High-performance pseudocapacitive anodes: Precision engineering of MoO3 thin films on nickel microparticles-enhanced carbon cloth for advanced supercapacitors - Pingzhong Fu; Nan Zhao; Lin Deng; Maoxin Luo; Jian Huang (Chemical Engineering Journal, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Potato–rice and garlic–rice rotation increases soil phosphorus availability through phosphate-solubiliing bacteria and root exudates in upland–paddy cropping systems - Qi Liu; Wei Zhou; Zhiping Yang; Tao Wang; Yong Fu; Xueping Yue; Haixiao Xia; Youfeng Tao; Fei Deng; Xiaolong Lei; Yong Chen; Wanjun Ren (Agriculture, Ecosystems & Environment, 2025)

miR-7002-5p targets caspase-1 to suppress the inflammatory response of macrophages induced by Streptococcus equi subsp. zooepidemicus - Honglin Xie; Jingfei Deng; Jingyu Yu; Shun Li; Yibo Wang; Yajuan Li; Yunfei Huang; Qinqin Sun; Jiedan Liao; Ziteng Deng; Qiang Fu (Archives of Microbiology, 2025)

Microbubble catalytic ozonation of refractory organic flotation reagents with steel slag and degradation pathways - Zeen Yu; Pingfeng Fu; Lianghua Wang; Yuliang Zhang; Wei Deng (Minerals Engineering, 2025)

Performance evaluation of La-Al bimetallic catalyst-assisted dielectric barrier discharge plasma degradation of sulfur hexafluoride - Jiaqi Li; Dinghao Deng; Runze Dong; Qian Yu; Dong Fu (Journal of Environmental Chemical Engineering, 2025)

Decrypting gene-spliced like and fast kinetic energy storage modes of Na/Mg dual doped manganese oxides cathode for high-performance aqueous zinc-ion batteries - Xiaosha Cui; Yaxiong Zhang; Qingfeng Wu; Sida Deng; Shengyuan Wang; Jiuzhou Wang; Yupeng Liu; Junli Zhang; Erqing Xie; Jiecai Fu (Chemical Engineering Journal, 2025)

Initiatorless solar-photopolymerized heterostructured hydrogel with high performance, environmental adaptability, and recyclability - Chenghao Wang; Ping Li; Mingming Deng; Lin Luo; Boyi Fu; Qi Liu; Chi Huang (Chemical Engineering Journal, 2025)

The PGC-1α/SIRT3 pathway mediates the effect of DON on mitochondrial autophagy and liver injury in mice - Yihan Wang; Jiali Fu; Danni Zhou; Zhihua Ren; Junliang Deng (Mycotoxin Research, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

Development of an Ellipsoid Based Chart Datum Around the China Seas - Yanguang Fu; Yanxiong Liu; Mehdi Khaki; Fukai Peng; Xiaolong Mi; Yikai Feng; Xiaoli Deng; Long Yang; Qinghua Tang; Li Cui (Marine Geodesy, 2025)

Selective extraction of lithium from coal gangue through calcination and mechanochemical activation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Guixia Fan; Jiushuai Deng; Xiaoyan Huang; Biao Fu (Journal of Environmental Management, 2025)

Response of soil profile greenhouse gas emissions to nitrogen fertilization: Three-year field observations and meta-analysis - Jin Liu; Yangquanwei Zhong; Jiajia Fu; Zhouping Shangguan; Lei Deng; Weiming Yan (Field Crops Research, 2025)

Marine octopus: global distribution, extraction methods, bioactive biomaterials, and biomedical applications - Mengfei Li; Zhihong Deng; Kun Cheng; Xianjun Fu; Xiuxue Li (Frontiers in Marine Science, 2025)
Octopus, an abundant marine species with diverse applications, is attracting growing attention for its unique biological characteristics and potential utilization in food science and biotechnology. Octopus contain amino acids, active peptides, fatty acids and trace elements and these bioactives exhibit a wide range of effects, including anti-bacterial, anti-tumor, antioxidant and anti-aging activities. The structure of octopus arm and suckers provides biomimetic design inspiration for tissue engineering and the regenerative ability of octopus provides reference for research in biomedical material. Therefore, this review systematically summarizes the research progress on octopus resource distribution, extraction methods, nutrients, bioactive compounds substances and research on regeneration material, aiming to promote the development and utilization of octopus resources. Firstly, the extractions methods of octopus were systematically reviewed. Secondly, seven kinds of nutrients concluded were introduced to reveal the nutritional components of octopus. Finally, the application of octopus in biotechnology and the research progress on their regenerative ability were summarized. This review provides a basis and reference for octopus functional nutrients and application of octopus biomedical materials.

Thiophene-containing macrocycles: from zero to three dimensions in organic nanomaterials - Tonglin Yang; Tao Wang; Fu Deng; Shuwei Ma; Fangqi Yang; Ying Wei; Chunxiao Zhong; Linghai Xie (Science Bulletin, 2025)

Unveiling the deep-sea microplastic Odyssey: Characteristics, distribution, and ecological implications in Pacific Ocean sediments - Hua Deng; Yutao Fu; Lei Su; Daohua Chen; Xiguang Deng; Bo Hu; Yuye Chen; Yinan Deng (Journal of Hazardous Materials, 2025)

Remediation of As and Sb co-contaminated mine runoff by a pilot-scale aboveground permeable reactive barrier filled with multiple solid wastes-based reactive media - Wei Deng; Pingfeng Fu; Wentao Hu; Shan Li; Yuliang Zhang; Zeen Yu; Jia Li (Journal of Cleaner Production, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Synthesis of a novel polysaccharide natural functional monomer for imprinted hydrogel microsphere preparation and targeted recognition of anti-tumor drug 7-xylulose-10-deacetylpaclitaxel - Xiaodan Wu; Chengdong Nie; Mengqiong Deng; Linan Sun; Ying Wang; Jingru Zhao; Yujie Fu; Yourong Duan; Ying Sun (Journal of Environmental Chemical Engineering, 2025)

Control of sedimentary and diagenetic processes on the reservoir heterogeneity: A case study of the cretaceous carbonate reservoir in an onshore oilfield, Abu Dhabi - Yuting Peng; Yingxiao Fu; Hangyu Liu; Kaibo Shi; Bo Liu; Rubing Han; Xili Deng (Journal of African Earth Sciences, 2025)

An experimental study on coal permeability enhancement by water freezing cycles without effects on produced gas compositions: Implications for enhancing coalbed methane production - Baoxin Zhang; Xuehai Fu; Zhaobiao Yang; Junqiang Kang; Ze Deng (Fuel, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Impact of vegetation restoration on soil organic carbon fractions: A global meta-analysis - Xiaoshan Zhang; Jiajia Fu; Peiyan Ma; Guodong Diwu; Tiantian Li; Hongze Ma; Zhouping Shangguan; Lei Deng; Yangquanwei Zhong; Weiming Yan (Ecological Engineering, 2025)

Mussel-inspired MXene-functionalized sponge for solar-driven water purification: Photothermal-driven crude oil absorption, solar steam generation, and photothermal sterilization - Jingwen Zhang; Xiangyi Zhang; Bingjie Mai; Nuo Fu; Shuyu Wang; Bin Shang; Ziwei Deng (Chemical Engineering Journal, 2025)

Effects of tourmaline on anaerobic ammonia oxidation process: Mechanistic Understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Shan Qiu; Baojian Jing; Shuoqi Ren; Jue Wang; Mengxuan Deng; Mengqi Fu; Zhongqi Jiang; Fengxia Deng; Jinghui Wang; Jie Qiu (Chemical Engineering Journal, 2025)

Rapid degradation of frozen soil environments in thermokarst-affected alpine grasslands on the Qinghai-Tibet Plateau under climate change - Yuanhong Deng; Xiaoyan Li; Chao Yang; Fangzhong Shi; Shaojie Zhao; Sha Zhou; Chiyuan Miao; Ruiqiang Ding; Yongshuo H. Fu; Xiaofan Yang; Zhigang Wang (CATENA, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Effects of temperature on growth performance, gonad development, immunity, and antioxidant response of hybrid red tilapia (Oreochromis niloticus ♂ × Oreochromis aureus ♀) - Endalh Mekonnen; Yujie Deng; Yude Sun; Lanmei Wang; Jianjun Fu; Mingkun Luo; Zaijie Dong; Wenbin Zhu (Aquaculture International, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Optical properties of CDOM and assessing eutrophication by remote sensing of CDOM in the Zhanjiang Bay, China - Yafeng Zhong; Guo Yu; Dongyang Fu; Fajin Chen; Yafei Luo; Ruozhao Deng (Frontiers in Marine Science, 2025)
Based on the field survey data collected in winter (January, 2018) and spring (April, 2017), the characteristic variability of chromophoric dissolved organic matter (CDOM) in different seasons in Zhanjiang Bay was analyzed. The results demonstrated that CDOM absorption coefficient at 280 nm ( a g (280)) and the spectral slope from 275 to 295 nm (S 275-295 ) representing the molecular weight of CDOM could both maintain good correlations with salinity in winter and spring, indicating that CDOM was more likely to exist as a conserved substance during its migration in Zhanjiang Bay. The characteristics of CDOM and the weak correlation between Chlorophyll a (Chl a) and CDOM revealed that the influence of algal activity on CDOM was limited. In addition, this study also suggested the idea of using CDOM to track the eutrophication of a bay. Based on the acceptable correlation between a g (280) and reflectance band ratio (R rs (704)/R rs (492)) recorded in-situ , and eutrophication index (EI), a series of empirical models were developed to categorize and retrieve the eutrophication through a g (280) and were then used to Sentinel-2. The eutrophication assessment of Zhanjiang Bay was examined by CDOM remote sensing. This study provided a fresh approach to measuring eutrophication that could help regional environmental quality management organizations to make informed decisions.

Dynamic impacts of vegetation growth and urban development on microclimate and building energy consumption - Hanxun Fu; Yuanhao Jiao; Lirui Deng; Wei Wang (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effect of bromide ion on the formation and toxicity of halonitromethanes from Microcystis aeruginosa solution during UV/chloramine disinfection - Qi Xue; Qian Tang; Lin Deng; Wei Luo; Mingle Xia; Shuang Fu; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2025)

Formation of halonitromethanes, dichloroacetonitrile, and trichloromethane in the presence of E. coli and nitrophenols during UV/post-chlorination - Tao Wang; Qian Tang; Lin Deng; Chaoqun Tan; Yulin Fu; Jun Hu; Rajendra Prasad Singh (Journal of Hazardous Materials, 2025)

Emergy-based sustainability analysis and comprehensive evaluation of individual heating systems: A case study from rural northern China - Yun Deng; Xueling Ran; Yaohong Yu; Yongkun Fu; Sihao Ren; Mingyang Liu; Renjie Dong; Yuguang Zhou (Journal of Cleaner Production, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Sensitive detection of monosultap using a BSA-Cu nanocluster-based turn-off-on fluorescent sensor - Siying Che; Gaoqiong Deng; Tingyong Ling; Haiyan Fu; Yuanbin She (Food Control, 2025)

Bayesian operational modal analysis of two supertall buildings under Super Typhoon Saola - Haoran Pan; Fan Jiang; Jiurong Wu; Ting Deng; Jiyang Fu (Engineering Structures, 2025)

Thermoacoustoelasticity for Elastic Wave Propagation in Preheated and Prestressed Solid Rocks - Jian Yang; Li-Yun Fu; Tongcheng Han; Wubing Deng; Bo-Ye Fu (Rock Mechanics and Rock Engineering, 2025)

Mechanisms of urea combined with nitrification inhibitors on prompting cadmium uptake and accumulation in rape (Brassica napus L.) - Li Li; Lin Chen; Xin Fu; Zhong Hu; Qingru Zeng; Xiao Deng; Yang Yang; Si Luo (Plant and Soil, 2025)

Functional analysis of the woody oil crop Plukenetia volubilis L. LEC2 homolog PvoB3-69 in promoting regeneration - Jing-jing Yu; Shiling Deng; Jinhui Mo; Han Huang; Zeng-Fu Xu; Yi Wang (Plant Cell Reports, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Inter-annual and seasonal variations of meteorological drought and their drivers in the southwest karst region of China - Baowei Fu; Juanli Jing; Qifang Deng; Shunshun Ding (Environmental Science and Pollution Research, 2025)

Optimizing the thiosulfate-mediated zerovalent iron/persulfate activation systems: Trade-off between Fe(III)/Fe(II) cycling and quenching effects in environmental remediation - Maolin Wang; Mi Deng; Gang Zhao; Yanchun Fan; Tianwen Liu; Ying Huang; Lan Peng; Haoyang Fu; Shengqiong Fang (Journal of Environmental Management, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Experimental study of the effects of engine oil on gaseous and particulate emissions during gasoline/ethanol combustion - Zichao Meng; Feng Zhou; Xiongbo Duan; Jianqin Fu; Jingping Liu; Banglin Deng (Fuel, 2025)

Based on metabolomics and fourier transforms near infrared spectroscopy characterization of Lanxangia tsaoko chemical profile differences among fruit types and development of rapid identification and nutrient prediction models - Deng-Ke Fu; Wei-Ze Yang; Mei-Quan Yang; Tian-Mei Yang; Yuan-Zhong Wang; Jin-Yu Zhang (Food Bioscience, 2025)

Elevated hemoglobin adducts derived from crotonaldehyde in healthy smokers and oral cancer patients by nanoflow liquid chromatography tandem mass spectrometry☆ - Kai-Ting Fu; Deng-Chyang Wu; Hauh-Jyun Candy Chen (Chemico-Biological Interactions, 2025)

Analysis of heavy metal content and microbial characteristics in the pioneer plant soil system of typical manganese tailing ponds in Guangxi - Dong Zhao; Hua Deng; Lening Hu; Shunyun Ye; Yu Yang; Jiahui Fu; Shuyun Zhang (Plant and Soil, 2025)

Correction to: Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Cracking behavior and deterioration of strength characteristics of silty clay under drying-wetting cycles - Mei Dong; Yunpeng Deng; YuHan Fu (Bulletin of Engineering Geology and the Environment, 2025)

Dry season residual straw reduces nitrous oxide emissions during rice season in upland-paddy rotation systems by inhibiting soil denitrification - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Zhiping Yang; Yong Fu; Xueping Yue; Fei Deng; Xiaolong Lei; et al. (Biology and Fertility of Soils, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

U(VI) removal by zerovalent manganese modified corn straw biochar in acidic wastewater: Efficiency, characteristics and mechanism - Taotao Zeng; Yusong Fu; Min Yang; Qiqi Deng; Shengbin Chen; Yingjiu Liu; Jun Li (Chemosphere, 2025)

The migration pattern of oxidation fluids and its constraints on uranium mineralization in the Tamusu sandstone type uranium deposit of the Bayingobi Basin, China - Chengyong Zhang; Fei Xia; Wei Deng; Xu Liu; Qunxi Zhang; Beibei Shi; Haixiao Li; Yukun Fu (Sedimentary Geology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Enhancement of the rice protein solubility using industry-scale microfluidization and pH cycling: A mechanistic study - Zhaoying Li; Jun Chen; David Julian McClements; Yunfeng Lu; Aiping Fu; Qin Geng; Lizhen Deng; Ti Li; Chengmei Liu; Taotao Dai (Food Hydrocolloids, 2025)

Non thermoplastic 3D molding based on coordination crosslinking for on-demand customization carboxymethyl chitosan-based packaging bags - Yongfu Deng; Shuwen Luo; Wenxin Zhao; Fuxiang Wei; Chuanhui Xu; Lihua Fu; Baofeng Lin (Food Packaging and Shelf Life, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Facile preparation of inexpensive polysaccharides-based antibacterial sensor for all-round monitoring of humidity and temperature in grain storage - Yongfu Deng; Yuyan Shi; Qianzheng Zeng; Chuanhui Xu; Lihua Fu; Baofeng Lin (Chemical Engineering Journal, 2025)

Sewage surveillance revealed the seasonality and prevalence of respiratory syncytial virus and its implications for seasonal immunization strategy in low and middle-income regions of China - Ziqiang Zhang; Qingxiang Li; Fenglan He; Zengguo Wang; Chulong Zhu; Junling Tu; Haifeng Li; Liu Yi; Yao Deng; Songzhe Fu (Water Research, 2025)

The interplay of singlet oxygen and ABI4 in plant growth regulation - Zhong-Wei Zhang; Yu-Fan Fu; Guang-Deng Chen; Christiane Reinbothe; Steffen Reinbothe; Shu Yuan (Trends in Plant Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mitigating frost heave of a soil stabilized with sisal fiber exposed to freeze-thaw cycles - Fei Deng; Jianguo Lu; Xusheng Wan; Boshi Liu; Binlong Zhang; Hao Fu (Geotextiles and Geomembranes, 2025)

High-entropy design of Ruddlesden-Popper structured LNO for enhanced performance in proton solid oxide fuel cells - Mingming Zhang; Yinlin Chang; Weiyuan Xiang; Jiani Liu; Xiangbo Deng; Jing Zhou; Min Fu; Zetian Tao (Fuel, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

A Novel Coumarin Based Fluorescent Probe for Cu²⁺ Detection as well as Applications - Yunke Gao; Linlong Deng; Lei Xue; Yihan Cheng; Shuai Fu; Haibin Wang (Journal of Fluorescence, 2025)

Comammox rather than AOB dominated the efficient autotrophic nitrification-denitrification process in an extremely oxygen-limited environment - Yu Xiang; Xiaoming Song; Yilin Yang; Shuai Deng; Liwei Fu; Cheng Yang; Mengli Chen; Jia Pu; Han Zhang; Hongxiang Chai (Water Research, 2025)

Dual regulation of As release and soil environment by Fe(Ⅱ) assisted steel slag and coal fly ash: Effects and potential mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Hazardous Materials, 2025)

Multiscale revelation of asphalt morphology and adhesion performance evolution during stress relaxation process - Fu Xu; Jing Deng; Yizhou Liu; Huijun Xie; Zhengwu Long; Botao Dai; Hao Yang; Lingyun You; Chongzheng Zhu; Dongzhao Jin (Fuel, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Assembly of SiO2@MXene spheres in PCN/Fe3C nanofibers with multifunctional electromagnetic wave absorption - Jun Huang; Xiaojun Zeng; Xiao Jiang; Xiaomei Deng; Qianqian Fu; Yu Xie; Yanfeng Gao (Chemical Engineering Journal, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Enabling high-efficiency ambient-air printable carbon-based large-area perovskite solar cells via effective anionic passivation - Yufei Fu; Wu Shao; Zhihao Deng; Wenjun Wu (Chemical Engineering Journal, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Candidatus Thiothrix phosphatis SCUT-1: A novel polyphosphate-accumulating organism abundant in the enhanced biological phosphorus removal system - Liping Chen; Xuhan Deng; Xiaojing Xie; Kaiying Wang; Hang Chen; Sheqi Cen; Fu Huang; Cenchao Wang; Yaqian Li; Chaohai Wei; Guanglei Qiu (Water Research, 2024)

Sedimentary antimony stable isotope record of anthropogenic contamination in a karst lake in southwestern China - Qianwen Deng; Xian Wu; Hui Zhang; Yunjie Wu; Kaihui Tang; Ye Sun; Guangyi Sun; Heng Yao; Jonas Olof Sommar; Xuewu Fu; Xinbin Feng (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

Study on selective green leaching of rare earth elements from coal gangue using mechanochemical activation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Yingqiu Wu; Guixia Fan; Biao Fu; Lin Ma; Yuntao kang; Xin Sun; Jiushuai Deng (Journal of Environmental Chemical Engineering, 2024)

Variations in volatile components and biological activities of essential oils from Citrus aurantium ‘changshanhuyou’ at different growth and ripening stages - Han Wang; Xinyue Zhou; Yong Deng; Ruyu Zhang; Kai Fu; Jiabao Huang; Qiong Huang; Cheng Zeng; Donghong Liu; Wenjun Wang (Food Research International, 2024)

Based on whole genome sequencing and metabolomics analysis the safety and probiotic characteristics of Lacticaseibacillus paracasei 36 isolated from Chinese fermented vegetables - Fei Wang; Xiang Li; Qi Wang; Qian Jin; Aikun Fu; Qiao Zhang; Rongchang Yang; Bin Deng; Weifen Li (Food Bioscience, 2024)

Transcriptomic reveals the effect of tannic acid stress on the cellular structure and growth of Saccharomyces cerevisiae - Yixin Huang; Mengfei Deng; Yanru Chen; Wenqin Cai; Na Liu; Yin Wan; Xiaodan Wu; Guiming Fu (Food Bioscience, 2024)

A flexible and superhydrophobic PVDF-HFP@PVA bilayer enables high-performance radiative cooling and thermal management - Jun-Heng Fu; Qigong Zhang; Minglei Yan; Wei Tang; Yun Zeng; Yuntao Cui; Mingkuan Zhang; Hongwei Deng; Hao Kang; Xinlong Sun; Liang Qiao; Hongzhang Wang; et al. (Chemical Engineering Journal, 2024)

Genetic characteristics and pathogenicity of variant porcine parvovirus 1 in northern China - Huiwei Deng; Mengting Wang; Guangyi Cong; Fang Fu; Li Feng (Veterinary Microbiology, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Finite difference solution for contaminant transport through a GCL composite cutoff wall-aquifer system considering semipermeable membrane effect - He-Fu Pu; Sheng-Yi Deng; Ming Min; Yong-Wei Zhou (Journal of Hydrology, 2024)

Biofilm enhanced the mitigations of antibiotics and resistome in sulfadiazine and trimethoprim co-contaminated soils - Zhi Mei; Fang Wang; Yuhao Fu; Yu Liu; Syed A. Hashsham; Yu Wang; Jean Damascene Harindintwali; Qingyuan Dou; Marko Virta; Xin Jiang; Yu Deng; Tong Zhang; et al. (Journal of Hazardous Materials, 2024)

Indicative impacts of sludge properties and biological metabolic characteristics on high-rate contact stabilization process performance - Zhongqi Jiang; Mengxuan Deng; Shan Qiu; Mengqi Fu; Mu Yuan; Qinxue Wen; Xinghua Jia (Journal of Environmental Management, 2024)

3D mineral prospectivity modeling using deep adaptation network transfer learning: A case study of the Xiadian gold deposit, Eastern China - Jin Chen; Xin Zuo; Zhankun Liu; Liqun Jiang; Yuezhi Li; Zhengkai Fu; Hao Deng; Xiancheng Mao (Geochemistry, 2024)

Modulation of acid-induced pea protein gels by gellan gum and glucono-δ-lactone: Rheological and microstructural insights - Changhong Li; Taotao Dai; Deyu Jiang; Guowen Zhang; Lizhen Deng; Ti Li; Ruihong Liang; Hengtang Dai; Aiping Fu; Chengmei Liu; Jun Chen (Food Research International, 2024)

Rosa roxburghii Tratt (Cili) has a more effective capacity in alleviating DSS-induced colitis compared to Vitamin C through B cell receptor pathway - Xiang Li; Qi Wang; Fei Wang; Qian Jin; Bin Deng; RongChang Yang; Aikun Fu; Fuyong Li; Qiao Zhang; Weifen Li (Food Research International, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

Anti-seepage performance and oxygen barrier performance of the three-layered landfill cover system comprising neutralized slag under extreme climate conditions - Ming Min; He-Fu Pu; Xiao He; Sheng-Yi Deng (Engineering Geology, 2024)

High salt-resistant and robust MXene@oleylamine/PET composite nonwoven for efficient and long-term solar desalination - Quanpei Xie; Shengwu Deng; Yong Wen; Yang Yang; Wenjie Fu; Jinxin Liu; Si Cheng (Chemical Engineering Journal, 2024)

Poly(ethylene oxide)-based composite solid electrolyte modified by Li7La3Zr2O12 inorganic filler with grafted imidazolium-based ionic liquids functional groups - Yanhua Zhang; Yumei Xiao; Zijun Tang; Liuli Zou; Qingting Liu; Xudong Fu; Xing Xiang; Jiadong Deng (Chemical Engineering Journal, 2024)

Effects of tourmaline on the establishment, idling, and recovery of partial nitrification: Mechanistic understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Baojian Jing; Jue Wang; Mengqi Fu; Mengxuan Deng; Shuoqi Ren; Zhongqi Jiang; Fengxia Deng; Shan Qiu (Chemical Engineering Journal, 2024)

Designing flexible TiO2/SrTiO3/BiOBr recyclable fiber membrane with spatial dual oxidation sites for photocatalytic uranium extraction under visible light - Zhenyu Cai; Jingjing Wang; Hao Fu; Yuehua Pan; Mingyue Ma; Yuqian Zhong; Yuxiang Deng; Yuezhou Wei; Toyohisa Fujita; Xinpeng Wang (Chemical Engineering Journal, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

An innovative strategy to enhance the interfacial interaction and effective contribution of BN in thermal conductivity in aramid based composites films - Yun Wei; Ming Wen; Yong Wen; Qichao Wen; Jie Wen; Qiang Fu; Hua Deng (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

On theoretical and practical analyses of BDS-3/Galileo/GPS all-in-view and PPP time transfer with the consideration of satellite clock biases - Dong Zhang; Fu Zheng; Meng Wang; Yuanhui Lin; Liangcheng Deng; Zhen Wang; Chuang Shi (Journal of Geodesy, 2024)

Corrigendum to ``Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions'' [Water Research 261 (2024) 122054] - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

Arsenic activated GLUT1-mTORC1/HIF-1α-PKM2 positive feedback networks promote proliferation and migration of bladder epithelial cells - Zhushan Fu; Meiqi Deng; Qing Zhou; Sihao Li; Weijue Liu; Siyan Cao; Lei Zhang; Yu Deng; Shuhua Xi (Science of The Total Environment, 2024)

Greenhouse gas emissions during the rice season are reduced by a low soil C:N ratio using different upland-paddy rotation systems - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Chunlian Jin; Wenwen Song; Fei Deng; Xiaolong Lei; Youfeng Tao; et al. (Field Crops Research, 2024)

Remediation of As, Sb, and Pb co-contaminated mining soils by using Fe/C based solid wastes: Synergistic effects and field applications - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Wen Ni; Siqi Zhang; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Flexible, wearable triboelectric rubber with tunable surface charge density enabled by regulation of surface functional group density and permittivity - Junjie Lu; Zehua He; Zihao Lin; Xianwei Deng; Bai Huang; Baofeng Lin; Lihua Fu; Chuanhui Xu (Chemical Engineering Journal, 2024)

Remediation of multiple heavy metals contaminated soils by Mn and Fe-added solid wastes: Effect and mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Genesis of Pb–Zn-Ag-Sb mineralization in the Tethys Himalaya, China: Early magmatic-hydrothermal Pb–Zn(-Ag) mineralization overprinted by Sb-rich fluids - Xiang Sun; Ru-Yue Li; Hao-Yu Sun; Paul H. Olin; M. Santosh; Bin Fu; Jun Deng (Mineralium Deposita, 2024)

Adaptive roles of cytokinins in enhancing plant resilience and yield against environmental stressors - Nishbah Mughal; Noman Shoaib; Jianhua Chen; Yang li; Yuhong He; Man Fu; Xingyun Li; Yuanyuan He; Jinya Guo; Juncai Deng; Wenyu Yang; Jiang Liu (Chemosphere, 2024)

Temporal shifts in the phytoplankton network in a large eutrophic shallow freshwater lake subjected to major environmental changes due to human interventions - Guojun Cai; Yili Ge; Zheng Dong; Yu Liao; Yaoqi Chen; Aiping Wu; Youzhi Li; Huanyao Liu; Guixiang Yuan; Jianming Deng; Hui Fu; Erik Jeppesen (Water Research, 2024)

Molecular-level insights into dissolved organic matter and its variations of the full-scale processes in a typical petrochemical wastewater treatment plant - Min Li; Zhouyang Li; Liya Fu; Liyan Deng; Changyong Wu (Water Research, 2024)

Targeting m6A mRNA demethylase FTO alleviates manganese-induced cognitive memory deficits in mice - Yi Wen; Zhushan Fu; Jiashuo Li; Mingyue Liu; Xinmiao Wang; Jingqi Chen; Yue Chen; Haocheng Wang; Sihang Wen; Ke Zhang; Yu Deng (Journal of Hazardous Materials, 2024)

Experimental investigation on the turbulence flame autoignition characteristics of ammonia in a high-temperature co-flow - Meng Ji; Zhijun Wu; Alessandro Ferrari; Oscar Vento; Quanbo Shang; Guanyu Zhang; Lezhong Fu; Jun Deng; Liguang Li (Fuel, 2024)

Advances in the delivery and application of antimicrobial peptide-based nanomaterials - Haoran Deng; Shaohua Zhang; Yanxue Fu; Na Dong; Chongpeng Bi; Anshan Shan; Changxuan Shao (Chemical Engineering Journal, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

YAP1 inhibits RSL3-induced castration-resistant prostate cancer cell ferroptosis by driving glutamine uptake and metabolism to GSH - Xian Fu; Hongshen Wu; Changjiu Li; Gang Deng; Chao Chen (Molecular and Cellular Biochemistry, 2024)
High levels of YAP1 and ferroptosis activation in castration-resistant prostate cancer (CRPC) can inhibit CRPC progression and improve its sensitivity toward chemotherapeutics drugs. However, whether YAP1 regulates ferroptosis in CRPC cells and the underlying mechanisms are unknown. The protein levels of YAP1, SLC1A5, and GLS1 in benign prostatic hyperplasia (BPH), prostate cancer (PCa) that did not progress to CRPC, and CRPC tissue samples were evaluated using western blotting. In PC-3 and DU-145 cells, YAP1 overexpression vector, small-interfering RNA, specific inhibitor verteporfin, ferroptosis-inducer RSL3, SLC1A5-inhibitor V-9302, and GLS1-inhibitor CB-839 were used. Immunofluorescence, flow cytometry, dual-luciferase reporter gene, and related kits were used to investigate the effect of YAP1 on the ferroptosis activity in CRPC cells and its underlying mechanisms. YAP1 promoted extracellular glutamine uptake and subsequent production of glutamate and glutathione (GSH), and increases the GPX4 activity. For the activation of ferroptosis by RSL3, YAP1 decreased the levels of reactive oxygen species, malondialdehyde, and lipid peroxidation, and the proportion of dead cells. Mechanistically, YAP1 promoted the expression of SCL1A5 and GLS1 and further increased the GSH levels and GPX4 activity. Thus, inhibiting SLC1A5 or GLS1 activity could alleviate the antagonistic effect of YAP1 on the ferroptosis of RSL3-induced CRPC cells. In CRPC, the YAP1 level is high, which enters the nucleus and promotes the expressions of SLC1A5 and GLS1, thereby promoting cellular glutamine uptake and metabolism to generate glutamate and further synthesizing GSH, increasing GPX4 activity, improving cellular antioxidant capacity, and inhibiting cell death.

Unveiling the overlooked threat: antibiotic resistance in groundwater near an abandoned sulfuric acid plant in Xingyang, China - Wei Yuan; Yafei Liu; Ruihao Liu; Leicheng Li; Peiyuan Deng; Shuai Fu; Luqman Riaz; Jianhong Lu; Guoting Li; Ziyan Yang (Environmental Geochemistry and Health, 2024)

A new algorithm of critical control rod position search in MC code - Rui Li; Yuanguang Fu; Peng Liu; Dunfu Shi; Li Deng; Haibo Xu (Annals of Nuclear Energy, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Effects of Fe(III) on the formation and toxicity alteration of halonitromethanes, dichloroacetonitrile, and dichloroacetamide from polyethyleneimine during UV/chlorine disinfection - Tingting Huang; Lin Deng; Shui Wang; Chaoqun Tan; Jun Hu; Bingqing Zhu; Mengya Li; Lianghua Lu; Zhihua Yin; Bowen Fu (Water Research, 2024)

Geochemical and biological evidence for the presence of secondary microbial gas in anthracite: A case study in the songta block, northern Qinshui Basin, China - Haijiao Fu; Kangjun Yang; Yueguo Li; Detian Yan; Zhan Zhou; Tuo Deng; Xianbo Su; Gang Wang; Shuguang Yang (International Journal of Coal Geology, 2024)

Quantitative assessment of the impact factors upon remediation performance of the PRB technique in conjunction with pumping/recharge - Han Xiao; Yu Yang; Xiangjian Xu; Sheng Deng; Xu Han; Fu Xia; Yonghai Jiang (Groundwater for Sustainable Development, 2024)

Activity of CuCoCe layered double hydroxides catalysts and mechanism for C3H6-SCR - Jiayin Chen; Wei Fu; Chen Cai; Shuying Ning; Muhammad Kashif; Wenyi Deng; Bingtao Zhao; Yaxin Su (Fuel, 2024)

Partially amorphization induced S-scheme charge migration in g-C3N4/Mn1.1Fe1.9O4 defective heterojunction for boosting fenton-like degradation of tetracycline under visible light - Siyue Huo; Jingrui Deng; Quanyou Zhao; Yichao Wang; Wenxian Fu; Xuan Wu; Mengchun Gao; Haijiao Xie (Chemical Engineering Journal, 2024)

New dawn of ginsenosides: regulating gut microbiota to treat metabolic syndrome - Xue Bai; Rongzhan Fu; Jianjun Deng; Haixia Yang; Chenhui Zhu; Daidi Fan (Phytochemistry Reviews, 2024)

Tanshinone IIA, originated from Salvia miltiorrhiza, activated EPO/EPOR-JAK2-STAT5 pathway in rat blood deficiency therapy - Miao Wang; Zhihong Deng; Congwei Shi; Kun Cheng; Runxiang Zhai; Xiuxue Li; Xianjun Fu (South African Journal of Botany, 2024)

Transient analytical solution for coupled water–gas transport in unsaturated soil cover of landfill - He-Fu Pu; Ming Min; Sheng-Yi Deng; Xiao-Jun Wen; Jun Xu (Journal of Hydrology, 2024)

Soot nanoparticles promote ferroptosis in dopaminergic neurons via alteration of m6A RNA methylation in Parkinson’s disease - Jiezhu Feng; Piao Zhang; Kunlin Chen; Peiting Huang; Xiaomei Liang; Jiawei Dong; Baoyu Zhu; Zhongling Fu; Tongtong Deng; Linyan Zhu; Chengyu Chen; Yuhu Zhang (Journal of Hazardous Materials, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

The role of Pm-miR-184-3p in regulating the immune response in the pearl oyster Pinctada fucata martensii - Shirong Fu; Yuting Zhang; Yu Jiao; Qingheng Wang; Yuewen Deng; Xiaodong Du (Fish & Shellfish Immunology, 2024)

Chiral dual-core emitters based-on through-space coupling for high-performance OLEDs with little efficiency roll-off - Lifen Chen; Mingjia Deng; Shao-Yun Yin; Yu Fu; Yingxiao Mu; Jia-Xiong Chen; Lingyun Cui; Shaomin Ji; Yanping Huo; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Implementation of Viscoelastic Artificial Boundary and Seismic Motion Input Method in Three-Dimensional Discontinuous Deformation Analysis Method - Si-huang Lin; Tao Deng; Lu Zheng; Hong Zhang; Wei Wu; Xiao-dong Fu; Guang-qi Chen (Rock Mechanics and Rock Engineering, 2024)

Cortical and spinal responses to short-term strength training and detraining in young and older adults in rectus femoris muscle - Gonzalo Gomez-Guerrero; Janne Avela; Ilkka Jussila; Esa Pihlajamäki; Fu-Yu Deng; Dawson J. Kidgell; Juha P. Ahtiainen; Simon Walker (European Journal of Applied Physiology, 2024)
Introduction Strength training mitigates the age-related decline in strength and muscle activation but limited evidence exists on specific motor pathway adaptations. Methods Eleven young (22–34 years) and ten older (66–80 years) adults underwent five testing sessions where lumbar-evoked potentials (LEPs) and motor-evoked potentials (MEPs) were measured during 20 and 60% of maximum voluntary contraction (MVC). Ten stimulations, randomly delivered, targeted 25% of maximum compound action potential for LEPs and 120, 140, and 160% of active motor threshold (aMT) for MEPs. The 7-week whole-body resistance training intervention included five exercises, e.g., knee extension (5 sets) and leg press (3 sets), performed twice weekly and was followed by 4 weeks of detraining. Results Young had higher MVC (~ 63 N·m, p = 0.006), 1-RM (~ 50 kg, p = 0.002), and lower aMT (~ 9%, p = 0.030) than older adults at baseline. Young increased 1-RM (+ 18 kg, p < 0.001), skeletal muscle mass (SMM) (+ 0.9 kg, p = 0.009), and LEP amplitude (+ 0.174, p < 0.001) during 20% MVC. Older adults increased MVC (+ 13 N·m, p = 0.014), however, they experienced decreased LEP amplitude (− 0.241, p < 0.001) during 20% MVC and MEP amplitude reductions at 120% (− 0.157, p = 0.034), 140% (− 0.196, p = 0.026), and 160% (− 0.210, p = 0.006) aMT during 60% MVC trials. After detraining, young and older adults decreased 1-RM, while young adults decreased SMM. Conclusion Higher aMT and MEP amplitude in older adults were concomitant with lower baseline strength. Training increased strength in both groups, but divergent modifications in cortico-spinal activity occurred. Results suggest that the primary locus of adaptation occurs at the spinal level.

A novel hierarchical approach to insight to spectral characteristics in surface water of karst wetlands and estimate its non-optically active parameters using field hyperspectral data - Bolin Fu; Sunzhe Li; Zhinan Lao; Yingying Wei; Kaishan Song; Tengfang Deng; Yeqiao Wang (Water Research, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Study on dynamic response characteristics of shallow buried pipe gallery structure under vehicle vibration load - Botuan Deng; Xiejin Zheng; Chaofan Shen; Yifan Fu (Soil Dynamics and Earthquake Engineering, 2024)

Efficient regulation of cadmium accumulation by carboxymethylammonium chloride in rice: Correlation analysis and expression of transporter gene OsGLR3 - Lin Fu; Jiawei Deng; Shuangyue Liu; Changbo Zhang; Weijie Xue; Gilles Mailhot; Davide Vione; Yun Deng; Changrong Wang; Lei Wang (Science of The Total Environment, 2024)

Underlying mechanisms governing on distribution and stratification of DOM during seasonal freeze-thaw cycles - Weiying Feng; Yuxin Deng; Fang Yang; Tingting Li; Fu Wang; Qi Zhang; Haipeng Yao; Haiqing Liao (Science of The Total Environment, 2024)

Exposure to the environmental pollutant chlorpyrifos induces hepatic toxicity through activation of the JAK/STAT and MAPK pathways - Huiyang Fu; Yao Ge; Xiyuan Liu; Siwei Deng; Jun Li; Peng Tan; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2024)

Quantifying vegetation species functional traits along hydrologic gradients in karst wetland based on 3D mapping with UAV hyperspectral point cloud - Bolin Fu; Liwei Deng; Weiwei Sun; Hongchang He; Huajian Li; Yong Wang; Yeqiao Wang (Remote Sensing of Environment, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A coupled PSR-based framework for holistic modeling and flood resilience assessment: A case study of the 2022 flood events in five southern provinces of China - Xingfeng Fu; Yun Liu; Zhiqiang Xie; Fengshan Jiang; Jiarui Xu; Zhibing Yang; Zhanting Deng; Qisheng Wang; Mengfan Liao; Xiaodong Wu; Zhanhui Wang; Qingyun Du (Journal of Hydrology, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Pretreatment of wastepaper with an aqueous solution of amino acid-derived ionic liquid for biochar production as adsorbent - Yi Jia; Shuai Nian; Wenxia Zhao; Lin Fu; Xiaokai Zhang; Ian Beadham; Shuchang Zhao; Changbo Zhang; Yun Deng (Journal of Environmental Management, 2024)

Proposal and application of a novel isothermal model for the thermodynamic study of ion exchange reactions - Caifang Cao; Yong Li; Ailin Fu; Gengfeng Deng; Xiaowen Li; Yupeng Li; Xiaochen Qiu (Chemical Engineering Journal, 2024)

Bromide Enhanced the Formation and Transformation of Halonitromethanes from Diatom Solution in the UV/NH2Cl Disinfection Process - Yuyang Mao; Tao Wang; Lin Deng; Shuang Fu; Jun Hu; Rajendra Prasad Singh (Water, Air, & Soil Pollution, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

The impact of air pollution on residents’ health in China: the mediating effect of population migration - Jianru Fu; Haifeng Fu; Chaoping Zhu; Ying Sun; Honghao Cao; Xin Deng (Air Quality, Atmosphere & Health, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

The sphingolipids change in exosomes from cancer patients and association between exosome release and sphingolipids level based on a pseudotargeted lipidomics method - Kaige Yang; Wenchang Fu; Mengjiao Deng; Xinyan Li; Mingyuan Wu; Yan Wang (Analytica Chimica Acta, 2024)

Evolved Late Mesozoic continental arc: Constraints of detrital zircons from the western East China Sea - Yuling Deng; Changhai Xu; Shunli Gao; Qiang Fu; Yuanyuan Li (International Geology Review, 2024)

A review of solid wastes-based stabilizers for remediating heavy metals co-contaminated soil: Applications and challenges - Yuliang Zhang; Pingfeng Fu; Wen Ni; Siqi Zhang; Sheng Li; Wei Deng; Wentao Hu; Jia Li; Fuyun Pei; Linfeng Du; Yueling Wang (Science of The Total Environment, 2024)

Boosted efficiency and unsaturated material stock growth in China's megacities: Accelerating as urbanization approaches 80 % - Chenling Fu; Tianjie Deng; Yan Zhang (Resources, Conservation and Recycling, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Frequency-domain prediction method for vortex/wake-induced vibrations of double flexible risers in tandem arrangements - Bing Zhao; Shixiao Fu; Pengqian Deng; Mengmeng Zhang; Yingli Bai; Xuepeng Fu (Ocean Engineering, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Authenticity identification of high – Temperature Daqu Baijiu through multi-channel visual array sensor of organic dyes combined with smart phone App - Yanmei Zhu; Fushuang Xiang; Yuanyuan Su; Xue Jiang; Yipeng Cang; Wanjun Long; Wei Lan; Gaoqiong Deng; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2024)

A double network facilitated ion-electron conductor for thermoelectric harvesting with high energy density - Mao Zhang; Qiang Fu; Hua Deng (Chemical Engineering Journal, 2024)

Evolutionary correlates of extinction risk in Chinese angiosperm - Yaojun Ye; Quansheng Fu; Sergei Volis; Zhimin Li; Hang Sun; Tao Deng (Biological Conservation, 2024)

Identification and validation of major and stable quantitative trait locus for falling number in common wheat (Triticum aestivum L.) - Zhi Li; Qinyi Luo; Yujie Gan; Xinli Li; Xia Ou; Yawen Deng; Shulan Fu; Zongxiang Tang; Feiquan Tan; Peigao Luo; Tianheng Ren (Theoretical and Applied Genetics, 2024)

Correction to: Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Effect of long-term dry–wet circulations on the Solidification/stabilization of Municipal solid waste incineration fly ash using a novel cementitious material - Wei Deng; Pingfeng Fu; Jia Li; Xiaoli Wang; Yuliang Zhang (Environmental Science and Pollution Research, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effect of melatonin on cryopreservation of Beijing you chicken (gallus gallus) spermatozoa - Laiqing Yan; Junying Li; Guangdong Li; Wenkui Ma; Yunjie Liu; Xuening Liu; Mengmeng Zhao; Pengyun Ji; Yao fu; Qihao Zheng; Xuemei Deng; Guoshi Liu (Cryobiology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Weakening Indian monsoon favors vegetation growth in humid but not in semi-arid ecosystems - Lijun Deng; Yang Fu; Xiaoxia Li; Zhuosong Geng; Jingtian Zhang; Junhe Chen; Dou Li; Jian Sun; J．Julio Camarero; Eryuan Liang (Agricultural and Forest Meteorology, 2024)

Larger hydroxyapatite aggregation from Ca2+ adhesion in ANAMMOX granular sludge caused by high dissolved oxygen - Mu Yuan; Shan Qiu; Mengqi Fu; Mengxuan Deng; Jue Wang; Fengxia Deng (Chemosphere, 2024)

Numerical simulation method and deterioration analysis of load-bearing performance of tunnel linings containing cold joints in plain concrete - Huang-Shi Deng; He-Lin Fu; Yi-Min Wu; Yi-Bo Zhao; Hai-Dong Yi (Tunnelling and Underground Space Technology, 2024)

Physical activity can reduce the risk of blood cadmium and blood lead on stroke: Evidence from NHANES - Xiaoqi Deng; Dichuan Liu; Miao Li; Jie He; Yufan Fu (Toxicology and Applied Pharmacology, 2024)

Weakened casual feedback loops following intensive restoration efforts and climate changes in a large shallow freshwater lake - Hui Fu; Yili Ge; Guojun Cai; Jianmin Deng; Huanyao Liu; Aiping Wu; Youzhi Li; Wei Li; Guixiang Yuan; Erik Jeppesen (Science of The Total Environment, 2024)

Designing Z-scheme In2O3 @ZnIn2S4 core-shell heterojunctions for enhanced photocatalytic multi-pollutant removal - Hao Fu; Yuxiang Deng; Zhenyu Cai; Yuehua Pan; Libo Yang; Toyohisa Fujita; Nannan Wang; Youbin Wang; Xinpeng Wang (Journal of Hazardous Materials, 2024)

Experimental study on the regulation of NOX in co-pyrolysis of maize straw and woody biomass - Yongkun Fu; Yaohong Yu; Jinglun Qiang; Yun Deng; Sihao Ren; Hussien Elshareef; Huan Li; Renjie Dong; Yuguang Zhou (Fuel, 2024)

A colorimetric and phosphorescent dual-mode nanosensing platform for the sensitive detection of tobramycin in dairy products - Songlin Liu; Mina Wang; Hui Deng; Xin Deng; Ying Xiong; Qian Wen; Wang Li; Jiali Ren; Xiangjin Fu; Yanni Chen (Food Bioscience, 2024)

Modeling denitrification nitrogen losses in China's rice fields based on multiscale field‐experiment constraints - Huayan Zhang; Wulahati Adalibieke; Wenxin Ba; Klaus Butterbach‐Bahl; Longfei Yu; Andong Cai; Jin Fu; Haoming Yu; Wantong Zhang; Weichen Huang; Yiwei Jian; Wenjun Jiang; et al. (Global Change Biology, 2024)
Denitrification plays a critical role in soil nitrogen (N) cycling, affecting N availability in agroecosystems. However, the challenges in direct measurement of denitrification products (NO, N 2 O, and N 2 ) hinder our understanding of denitrification N losses patterns across the spatial scale. To address this gap, we constructed a data‐model fusion method to map the county‐scale denitrification N losses from China's rice fields over the past decade. The estimated denitrification N losses as a percentage of N application from 2009 to 2018 were 11.8 ± 4.0% for single rice, 12.4 ± 3.7% for early rice, and 11.6 ± 3.1% for late rice. The model results showed that the spatial heterogeneity of denitrification N losses is primarily driven by edaphic and climatic factors rather than by management practices. In particular, diffusion and production rates emerged as key contributors to the variation of denitrification N losses. These findings humanize a 38.9 ± 4.8 kg N ha −1 N loss by denitrification and challenge the common hypothesis that substrate availability drives the pattern of N losses by denitrification in rice fields.

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Source, composition and molecular diversity of dissolved and particulate organic matter varied with riparian land use in tropical coastal headstreams - Hengkuan Ji; Hua Wang; Zhipeng Wu; Dengfeng Wang; Xilong Wang; Peijiao Fu; Caisheng Li; Wangang Deng (Science of The Total Environment, 2024)

Energy management for proton exchange membrane fuel cell-lithium battery hybrid power systems based on real-time prediction and optimization under multimodal information - Linghong Zeng; Jun Fu; Chuang Sheng; Beijia Li; Ziang Guo; Qian Xiang; Jingjing Wang; Xinkai Shan; Xiaowei Fu; Zhonghua Deng; Zhuo Wang; Xi Li (Journal of Cleaner Production, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Optimizing Microplastic Removal Through Coagulation-Sedimentation with Permanganate Pre-oxidation and Pre-chlorination - Haixuan Zhang; Haiyang Deng; Huase Ou; Ruijuan Liu; Yuheng Chen; Xinni Wu; Jianwei Fu (Water, Air, & Soil Pollution, 2024)

Effects of Water Saturation and Loading Condition on Rock Tensile Strength: Insights from Acoustic Emission Analysis - Jun Zhu; Jianhui Deng; Po Ning; Ziguo Fu; Xuankun Li; Ronald Y. S. Pak (Rock Mechanics and Rock Engineering, 2024)

Temporal dynamics of the microbial heterogeneity–diversity relationship in microcosmic systems - Wei Deng; Nong-En Bai; Fu-Liang Qi; Xiao-Yan Yang; Rong She; Wen Xiao (Oecologia, 2024)

Longitudinal wastewater surveillance of four key pathogens during an unprecedented large-scale COVID-19 outbreak in China facilitated a novel strategy for addressing public health priorities–A proof of concept study - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiqiang Deng; Fenglan He; Xiaotong Jiang; Lixin Shen (Water Research, 2023)

Chlorpyrifos induces placental oxidative stress and barrier dysfunction by inducing mitochondrial apoptosis through the ERK/MAPK signaling pathway: In vitro and in vivo studies - Jun Bai; Siwei Deng; Huiyang Fu; Qing Yang; Fazheng Ren; Shenming Zeng; Zhaohui Chen; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2023)

A novel 3D-fluorescence sensing strategy based on HN-chitosan polymer probe for rapid identification and quantification of potential adulteration in saffron - Wanjun Long; Gaoqiong Deng; Yanmei Zhu; Qingyang Han; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Exploring the stress mechanism of tannic acid on Saccharomyces cerevisiae based on transcriptomics - Mengxiang Li; Mengfei Deng; Yanru Chen; Haowei Fan; Yixin Huang; Yunhong Huang; Yin Wan; Guiming Fu (Food Bioscience, 2023)

Transcriptomic analysis revealed the dynamic response mechanism to acute ammonia exposure in the ivory shell, Babylonia areolata - Xin Hong; Jie Qin; Deng Fu; Yi Yang; Aimin Wang; Zhifeng Gu; Feng Yu; Chunsheng Liu (Fish & Shellfish Immunology, 2023)

Polyaniline/Polydopamine-Regulated Nitrogen-Doped Graphene Aerogel with Well-developed Mesoporous Structure for Supercapacitor Electrode - Xu Xiang; Zejiang Deng; Haifeng Zhang; Changqin Gao; Shi Feng; Zhihan Liu; Qiuyu Liang; Yufan Fu; Yuwei Liu; Kai Liu (Chemical Engineering Journal, 2023)

CDKN2B-AS1 mediates proliferation and migration of vascular smooth muscle cells induced by insulin - Hao-jie Jin; Zi-heng Wu; Bao-fu Zhang; Jie Deng; Yin-dong Xu; Xin-yu Wang; Zheng-yang Song; Xin-wu Lu; Wan-tie Wang; Xiang-tao Zheng (Cell and Tissue Research, 2023)

Accelerated electron and mass transfer through constructing H2WO4/Ti3C2/g-C3N4 Z-scheme photocatalyst for environmental remediation - Qiang Li; Erpeng Wang; Hao Zhou; Yangjie Fu; Hao Deng; Yazhuo Zheng; Biao Xue; Hao Du; Guoxiang Yang; Qi Wang; Zhimei Sun; Jian Zhou (Chemosphere, 2023)

Candidatus Accumulibacter use fermentation products for enhanced biological phosphorus removal - Liping Chen; Gengrui Wei; Yushen Zhang; Kaiying Wang; Cenchao Wang; Xuhan Deng; Yaqian Li; Xiaojing Xie; Jinling Chen; Fu Huang; Hang Chen; Bin Zhang; et al. (Water Research, 2023)

The factors controlling antibiotic resistance genes in different treatment processes of mainstream full-scale wastewater treatment plants - Zimu Wang; Li Fu; Ji-Dong Gu; Shihuai Deng; Chengyi Huang; Ling Luo (Science of The Total Environment, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Discovery and identification of a novel canine coronavirus causing a diarrhea outbreak in Vulpes - Yuting Liu; Yao Deng; Sheng Niu; Na Zhu; Jingdong Song; Xiaoshuang Zhang; Weiting Su; Wenhui Nie; Roujian Lu; David M. Irwin; George Fu Gao; Wenling Wang; et al. (Science Bulletin, 2023)

Knockout of SlbZIP68 reduces late blight resistance in tomato - Wenhui Yang; Chunxin Liu; Qingjun Fu; Xinyi Jia; Liping Deng; Chunying Feng; Yuhan Wang; Zhenru Yang; Huanhuan Yang; Xiangyang Xu (Plant Science, 2023)

Learning-Based personal models for joint optimization of thermal comfort and energy consumption in flexible workplaces - Min Deng; Bo Fu; Carol C. Menassa; Vineet R. Kamat (Energy and Buildings, 2023)

How to utilize neighborship: The role of residents' social capital in the neighborhood renewal in China - Ruopeng Huang; Guiwen Liu; Kaijian Li; Asheem Shrestha; Xinyue Fu; Kairui You; Xun Deng (Environmental Impact Assessment Review, 2023)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

Spatial pattern of hydrological and erosion behaviour along a dolomite hillslope in Southwest China - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (CATENA, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

Heat induced superfast diclofenac removal in Cu(II)–activated peracetic acid system: Mediation from non-radical to radical pathway - Jieli Ou; Jiewen Deng; Zhenran Wang; Yongsheng Fu; Yiqing Liu (Chemosphere, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

The combination of multiple linear regression and adaptive neuro-fuzzy inference system can accurately predict trihalomethane levels in tap water with fewer water quality parameters - Jianzhen Zhang; Duo Ye; Quanyou Fu; Minjie Chen; Hongjun Lin; Xiaoling Zhou; Wenjing Deng; Zeqiong Xu; Hongjie Sun; Huachang Hong (Science of The Total Environment, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Saturation-tolerant prescribed function-based adaptive fault-tolerant tracking control for ACV with uncertainty and faults - Fu Mingyu; Bai Dan; Deng Hanbo; Huang Sunan (Ocean Engineering, 2023)

Modeling and optimization of Graphene Oxide (GO) membranes for nanofiltration with artificial neural networks - Haodong Yang; Zhe Chen; Yong Li; Lei Yao; Geming Wang; Quanrong Deng; Ping Fu; Shenggao Wang (Journal of Water Process Engineering, 2023)

Differential effects of parental and developmental temperatures on larval thermal adaptation in oviparous and viviparous model fish species - Jigang Xia; Chuke Deng; Xueli Zheng; Yan Huang; Chris K. Elvidge; Shijian Fu (Journal of Thermal Biology, 2023)

Modeling potential arsenic enrichment and distribution using stacking ensemble learning in the lower Yellow River Plain, China - Wengeng Cao; Yu Fu; Yanpei Cheng; Wenhua Zhai; Xiaoyue Sun; Yu Ren; Deng Pan (Journal of Hydrology, 2023)

Online energy management optimization of hybrid energy storage microgrid with reversible solid oxide cell: A model-based study - Yihuan Zhou; Zhiping Xia; Xingbo Liu; Zhonghua Deng; Xiaowei Fu; Jakub Kupecki; Bing Jin; Xi Li (Journal of Cleaner Production, 2023)

Spherical-like Mo2C/ZnIn2S4 heterojunctions with boosting photo-carriers separation for effective tetracycline removal in water via synergistic adsorption and photocatalytic process - Gang Wu; Fu Liu; Maoqing Tian; Xionghui Deng; Xuxiang Zhang; Hongqiang Ren; Jinju Geng (Journal of Environmental Chemical Engineering, 2023)

A zinc-octacarboxylate MOF with an unusual (6, 8)-connected ocu topology for high-capacity adsorptive separation of C8 alkylaromatics - Xiuping Deng; Maojun Deng; Yu-Lin Li; Zewei Liu; Tian-Fu Liu; Xin Chen; Shuhan Cai; Biying Liu; Jiesen Li; Daofei Lv; Jing Li; Wenbing Yuan (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Organic solvent separation using carbon nanotube-interlayered thin film composite membrane - Luyao Deng; Ralph Rolly Gonzales; Wenming Fu; Guorong Xu; Ryosuke Takagi; Qiangqiang Song; Siyu Zhou; Hideto Matsuyama (Chemical Engineering Journal, 2023)

Scalable 3D textile with hierarchically functionalized pyramidal units using nanostructured polyamide@carbon/Fe3O4 fibers for tunable microwave absorption - Xiuyan Deng; Shuang Gao; Xiaoming Qi; Hongbo Dai; Shaoyun Fu; Qingqing Ni; Yaqin Fu (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

The role of semiannual cycle in modulating seasonality changes of surface air temperature over China and its mechanism - Qimin Deng; Yuting Wang; Xin Tan; Zuntao Fu (Climate Dynamics, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Experimental study on lateral impact resistance of the prestressed anchored rock mass - Fu Yu-Kai; Wu Yong-Zheng; Hao Deng-Yun (Arabian Journal of Geosciences, 2023)

Natural phosphorus-ferromanganese ore-based composites for the simultaneous remediation of arsenic- and lead-co-contaminated groundwater: synergistic effectiveness, kinetics, and mechanisms - Hongli Lu; Xiangjian Xu; Yu Yang; Han Xiao; Fu Xia; Xu Han; Sheng Deng; Shuxuan Wu; Xingang Wang; Yonghai Jiang; Qinghua Yan (Environmental Science and Pollution Research, 2023)

Bisphenol P and bisphenol M promote triple-negative breast cancer metastasis through activation of AKT pathways - Jinmi Liu; Haiping Wang; Xiaoying Hou; Limei Fan; Fang Yang; Yuhang Dai; Yufei Deng; Zhengqi Fu; Xiji Shu; Binlian Sun; Yuchen Liu (Science of The Total Environment, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

Lipopolysaccharide accelerates tryptophan degradation in the ovary and the derivative kynurenine disturbs hormone biosynthesis and reproductive performance - Jie Shen; Weimin Zhao; Juanru Cheng; Jinhua Cheng; Lei Zhao; Chaohui Dai; Yanfeng Fu; Bixia Li; Zhe Chen; Deshun Shi; Hui Li; Yanfei Deng (Journal of Hazardous Materials, 2023)

Phosphate enhanced Cu(II)/peracetic acid process for diclofenac removal: Performance and mechanism - Jiewen Deng; Jieli Ou; Zhenran Wang; Yongsheng Fu; Yiqing Liu (Environmental Research, 2023)

Low-δ18O and negative-Δ199Hg felsic igneous rocks in NE China: Implications for Early Cretaceous orogenic thinning - Changzhou Deng; Anzong Fu; Hongyan Geng; Deyou Sun; Guochun Zhao; Guangzhou Mao; Frédéric Moynier; Bernd Lehmann; Runsheng Yin (Chemical Geology, 2023)

PPARɑ Ligand Caudatin Improves Cognitive Functions and Mitigates Alzheimer’s Disease Defects By Inducing Autophagy in Mice Models - Senthilkumar Krishnamoorthi; Ashok Iyaswamy; Sravan Gopalkrishnashetty Sreenivasmurthy; Abhimanyu Thakur; Karthick Vasudevan; Gaurav Kumar; Xin-Jie Guan; Kejia Lu; Isha Gaurav; Cheng-Fu Su; Zhou Zhu; Jia Liu; et al. (Journal of Neuroimmune Pharmacology, 2023)

Developing and characterizing monoclonal antibodies of Guertu bandavirus nucleoprotein for developing methods of Guertu bandavirus and severe fever with thrombocytopenia syndrome virus detection - Jin Qian; Liyan Fu; Xiaoli Wu; Zhiying Wang; Hualin Wang; Yan Zeng; Guirong Cheng; Fei Deng; Shu Shen (Brazilian Journal of Microbiology, 2023)

Partial substitution of chemical fertilizer with organic fertilizer and slow-release fertilizer benefits soil microbial diversity and pineapple fruit yield in the tropics - Xin Jin; Jinwen Cai; Shuyun Yang; Shoupeng Li; Xujie Shao; Chunmin Fu; Changzhen Li; Yan Deng; Jiaquan Huang; Yunze Ruan; Changjiang Li (Applied Soil Ecology, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Co-exposure to parabens and triclosan and associations with cognitive impairment in an elderly population from Shenzhen, China - Xiaohu Ren; Yilan Deng; Wei Liu; Jinfeng Fu; Zhihong Huang; Duo Zhang; Qinru Xiao; Xiangyu Li; Xiao Chen; Xinfeng Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Comprehensive magnetic analysis of the tephras in Middle-Late Pleistocene loess records of Serbia, and implications for tephra identification, correlation and loess chronology - Namier Namier; Qingzhen Hao; Xinbo Gao; Yu Fu; Slobodan B. Marković; Ulrich Hambach; Daniel Veres; Joseph A. Mason; Yang Song; Chenglong Deng; Milivoj B. Gavrilov; Rastko Marković; et al. (Quaternary Science Reviews, 2023)

Organic matter enrichment in Asia's palaeolake controlled by the early and middle Eocene global warming and astronomically driven precessional climate - Xiaosong Wei; Yong Deng; Detian Yan; Entao Liu; Ping Jiang; Jiaxiong Zhou; He Huang; Bao Zhang; Haijiao Fu; Yin Gong (Marine and Petroleum Geology, 2023)

High-moisture extrusion of soy protein: Effects of insoluble dietary fiber on anisotropic extrudates - Qian Deng; Zhaojun Wang; Liwei Fu; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Food Hydrocolloids, 2023)

Application of stable isotope and mineral element fingerprint in identification of Hainan camellia oil producing area based on convolutional neural networks - Jiashun Fu; Junhao Wang; Zhe Chen; Zhuowen Deng; Hanggui Lai; Liangxiao Zhang; Yong-Huan Yun; Chenghui Zhang (Food Control, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Constitutive model for simulating the mechanical behaviour of rock under triaxial cyclic loading - Kaixun Hu; Helin Fu; Jie Li; Huangshi Deng (Computers and Geotechnics, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Solar radiation utilization of five upland–paddy cropping systems in low-light regions promoted by diffuse radiation of paddy season - Qi Liu; Zhiping Yang; Wei Zhou; Tao Wang; Yong Fu; Xueping Yue; Hong Chen; Youfeng Tao; Fei Deng; Xiaolong Lei; Wanjun Ren; Yong Chen (Agricultural and Forest Meteorology, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Editorial: Aquatic microorganism and their response to environment virulence and antimicrobial resistance - Yiqin Deng; Songzhe Fu; Learn-Han Lee; Juan Feng; Jie Huang (Frontiers in Marine Science, 2023)

FATP2 regulates non-small cell lung cancer by mediating lipid metabolism through ACSL1 - Yinghua Chen; Yu Zhao; Yuan Deng; Yan Yang; Lijun Xu; Jianwei Fu (Tissue and Cell, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Efficient utilization of biogenic manganese oxides in bioaugmentation columns for remediation of thallium(I) contaminated groundwater - Liangjing Zhang; Yu Yang; Xiangjian Xu; Sheng Deng; Han Xiao; Xu Han; Fu Xia; Yonghai Jiang (Journal of Hazardous Materials, 2023)

Is the petrochemical industry an overlooked critical source of environmental microplastics? - Liyan Deng; Hongbo Xi; Chunli Wan; Liya Fu; Yue Wang; Changyong Wu (Journal of Hazardous Materials, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Highly efficient reduction of nitrophenols by Fe-N-C single-atom catalyst: Performance and mechanism insights - Lei Qin; Wenfang Chen; Cui Lai; Shiyu Liu; Yukui Fu; Huchuan Yan; Fuhang Xu; Dengsheng Ma; Abing Duan; Hao Deng; Qi Yang; Yuyan Sun; et al. (Journal of Environmental Chemical Engineering, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Biomimetic superwetting CuSx–based composite mesh for wastewater treatment: Reversible oil/water separation, photocatalytic degradation and photothermal sterilization - Songyu Liu; Huichao Wang; Bin Shang; Nuo Fu; Jing Cao; Ziwei Deng (Journal of Environmental Chemical Engineering, 2023)

Accelerated hydrological cycle during the Toarcian oceanic anoxic event: Biomarker evidence in the Qiangtang Basin, eastern Tethys - Jianquan Yi; Xiugen Fu; Qiuding Du; Hengye Wei; Ahmed Mansour; Ying Nie; Yuhong Zeng; Jinxian Deng; Gang Zhou; Wenzhi Wang; Lijun Shen (Journal of Asian Earth Sciences, 2023)

The Intrinsic Relation between the Hydrogel Structure and In Vivo Performance of Hyaluronic Acid Dermal Fillers: A Comparative Study of Four Typical Dermal Fillers - Weiwei Zhou; Shuai Hou; Shu Deng; Yang Peng; Wei Fu; Yang Zhou; Jie Yang; Cheng Peng (Tissue Engineering and Regenerative Medicine, 2023)

Leaky Gut Plays a Critical Role in the Pathophysiology of Autism in Mice by Activating the Lipopolysaccharide-Mediated Toll-Like Receptor 4–Myeloid Differentiation Factor 88–Nuclear Factor Kappa B Signaling Pathway - Fang Li; Haoran Ke; Siqi Wang; Wei Mao; Cexiong Fu; Xi Chen; Qingqing Fu; Xiaori Qin; Yonghua Huang; Bidan Li; Shibing Li; Jingying Xing; et al. (Neuroscience Bulletin, 2023)
Increased intestinal barrier permeability, leaky gut, has been reported in patients with autism. However, its contribution to the development of autism has not been determined. We selected dextran sulfate sodium (DSS) to disrupt and metformin to repair the intestinal barrier in BTBR T + tf/J autistic mice to test this hypothesis. DSS treatment resulted in a decreased affinity for social proximity; however, autistic behaviors in mice were improved after the administration of metformin. We found an increased affinity for social proximity/social memory and decreased repetitive and anxiety-related behaviors. The concentration of lipopolysaccharides in blood decreased after the administration of metformin. The expression levels of the key molecules in the toll-like receptor 4 (TLR4)–myeloid differentiation factor 88 (MyD88)–nuclear factor kappa B (NF-κB) pathway and their downstream inflammatory cytokines in the cerebral cortex were both repressed. Thus, “leaky gut” could be a trigger for the development of autism via activation of the lipopolysaccharide-mediated TLR4–MyD88–NF-κB pathway.

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Face it and shoulder it jointly: from personal experience to mitigation behavior of climate change - Yuling Fu; Jiaxin Shi; Dan Su; Fumin Deng (Environment, Development and Sustainability, 2023)

A 209,000-year-old history of methane seepage activity controlled by multiple factors in the South China Sea - Ganglan Zhang; Jun Cao; Yinan Deng; Hongfei Lai; Xuexiao Jiang; Yunxin Fang; Zenggui Kuang; Shengxiong Yang; Qianyong Liang; Piaoer Fu; Tiantian Sun; Meng Jin; et al. (Marine and Petroleum Geology, 2023)

Experimental and simulation study on hydroxyl group promoting low-temperature oxidation of active groups in coal - Xun Zhang; Bing Lu; Jing Zhang; Xiang Fu; Hanzhong Deng; Ling Qiao; Cong Ding; Fei Gao (Fuel, 2023)

Analysis of risk factors associated with healthcare-associated carbapenem-resistant Klebsiella pneumoniae infection in a large general hospital: a case-case-control study - Wenzhi Huang; Fu Qiao; Yuhua Deng; Shichao Zhu; Jingwen Li; Zhiyong Zong; Wei Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Peanut shell biochar immobilized Pseudomonas hibiscicola strain L1 to remove electroplating mixed-wastewater - Qiang An; Binbin Ran; Shuman Deng; Ningjie Jin; Bin Zhao; Jiali Song; Siyu Fu (Journal of Environmental Chemical Engineering, 2023)

Desorption of cadmium from Fe Cd and recycle of Fe0: Experimental and mechanism study - Junhao Fu; Guanshuo Han; Haisheng Han; Ruohua Liu; Chaozheng Deng; Jianhua Kang; Tong Yue (Journal of Environmental Chemical Engineering, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Producing malonate in Saccharomyces cerevisiae via the β-alanine pathway - Shiyun Li; Wenxuan Fu; Ruifang Su; Yunying Zhao; Yu Deng (Systems Microbiology and Biomanufacturing, 2023)

Regional changes of surface air temperature annual cycle in the Northern Hemisphere land areas - Qimin Deng; Zuntao Fu (International Journal of Climatology, 2023)
The regional amplitude and phase characteristics of surface (2 m) air temperature (SAT) annual cycle (AC) over the Northern Hemisphere land area are analysed by the clustering method for the period 1953–2018. The five clusters are found in the nonlinear changes of AC amplitude and the six clusters are found in the AC phase. The spatial distributions of clusters are not the same for amplitude and phase, but the similarity is that both the amplitude and phase have remarkably different trends in the mainland of Eurasia and North America, even though these two regions locate over the similar latitudinal zone. Descending trends of AC amplitude are found for the whole period 1953–2018 in most areas, except in and around Greenland. However, when checking the nonlinear variation and making a piece‐wise linear fit, the abnormal increasing trend (stronger seasonality) appears in the major part of Eurasia after the year 1990. The comparisons of surface radiation fluxes in Eurasia and North America indicate that the long‐term reduction of the reflection and absorption of clouds and aerosols with the declined surface albedo after 1980–1985 may lead to the amplitude amplification after 1990 in Eurasia. In contrast, the variation of surface radiation in North America remains unchanged, where the decreasing trend of amplitude may result from other causes. The overall phase trend is increasing (toward earlier season), but in North America after 1990, the phase shift becomes delayed. The phase variations are correlated to North Atlantic Oscillation (NAO) cold season index over almost all regions, especially in Europe.

Multiple paths towards Eco islands and blue development: Conference report - Yuncheng Deng; Anica Čuka; Yanyan Fu; Jiangyue Wu (Marine Policy, 2023)

Seasonal source identification and formation processes of marine particulate water soluble organic nitrogen over an offshore island in the East China Sea - Mengke Tian; Hao Li; Guochen Wang; Mengxin Fu; Xiaofei Qin; Da Lu; Chengfeng Liu; Yucheng Zhu; Xingzhang Luo; Congrui Deng; Sabur F. Abdullaev; Kan Huang (Science of The Total Environment, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

A novel thermosensitive persulfate controlled-release hydrogel based on agarose/silica composite for sustained nitrobenzene degradation from groundwater - Shuxuan Wu; Sheng Deng; Fu Xia; Xu Han; Tianyu Ju; Han Xiao; Xiangjian Xu; Yu Yang; Yonghai Jiang; Beidou Xi (Journal of Hazardous Materials, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Carbonized waste polyphenylene sulfide non-woven decorated wood evaporator for clean water production from solar photothermal desalination - Lu Fu; Xiang Zhou; Liumi Deng; Meng Liao; Shaohua Chen; Hua Wang; Luoxin Wang (Desalination, 2023)

Dynamic variation of Paris polyphylla root-associated microbiome assembly with planting years - Shaodong Fu; Yan Deng; Kai Zou; Shuangfei Zhang; Zhenchun Duan; Xinhong Wu; Jin Zhou; Shihui Li; Xueduan Liu; Yili Liang (Planta, 2023)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Investigation and optimization of methane purification method for natural gas by two-column gas chromatography: A preliminary test for doubly substituted isotopologue (13CH3D) measurements - Tiantian Sun; Jun Cao; Haijun Qiu; Piaoer Fu; Hailong Lu; Zijie Ning; Daohua Chen; Yinan Deng; Shengxiong Yang (Frontiers in Marine Science, 2023)
In this study, optimization of the methane purification method by gas chromatography (GC) is described for the determination of methane clumped isotope compositions of natural gas. Methane was purified under the carrying of helium on the assembly line composed of a vacuum apparatus and two-column gas chromatography. Once methane was detected by the passive thermal conductivity detector (TCD) on the GC, it was collected through a silica trap immersed in liquid nitrogen. Optimum conditions of chromatographic column diameter (1/4 inch outside diameter), temperature (25 °C), and flow rate (50.8 ml min -1 ) have been determined. When N 2 /CH 4 (by volume) is<8.7%, the purification experiment can be undertaken once, while a double purification experiment is required when natural gas samples have an N 2 /CH 4 of 8.7-78.0%. The purification method yielded a purity of 98.4-98.8% with a recovery of 97.3-98.7% on purified methane samples verified by GC determination. N 2 was the main source that contributed to the loss of the purity, however, the N-bearing isobaric interferences ( 14 NH 3 + and 14 NH 4 + ) in purified samples presented<1‰ intensity compared to the methane isotopologues ( 13 CH 4 + and 13 CH 3 D + ), thus we concluded that these interferences have no impact on clumped isotope determinations. The conventional δ 13 C VPDB and δD VSMOW values of purified methane samples were consistent with those of pure methane. A preliminary measurement of Δ 13 CH 3 D (working gas) of purified samples revealed differences of -0.27‰, which was within the internal precision of the measurement. The entire process of a single purification can be completed within two hours. Our proposed method could be used for the clumped isotope purification of natural gas with higher than ~50% methane.

Identification of a 17β-estradiol-degrading Microbacterium hominis SJTG1 with high adaptability and characterization of the genes for estrogen degradation - Weiliang Xiong; Wanli Peng; Yali Fu; Zixin Deng; Shuangjun Lin; Rubing Liang (Journal of Hazardous Materials, 2023)

Purification and water resource circulation utilization of Cd-containing wastewater during microbial remediation of Cd-polluted soil - Yan Deng; Shaodong Fu; Menglong Xu; Hongwei Liu; Luhua Jiang; Xueduan Liu; Huidan Jiang (Environmental Research, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Out-of-plane dynamic parametric instability of circular arches with elastic rotational restraints under a localized uniform radial periodic load - Zixuan Kuang; Airong Liu; Jian Deng; Jiyang Fu (Engineering Structures, 2023)

Enhanced antibacterial effect and biodegradation of coating via dual-in-situ growth based on carboxymethyl cellulose - Zhenhao Lin; Hao Fu; Yuancheng Zhang; Yongfu Deng; Fuxiang Wei; Hao Li; Chuanhui Xu; Fuli Hua; Baofeng Lin (Carbohydrate Polymers, 2023)

Hybridization of carboxymethyl chitosan with bimetallic MOFs to construct renewable metal ion “warehouses” with rapid sterilization and long-term antibacterial effects - Hao Li; Yuwei Zhang; Yuancheng Zhang; Fuxiang Wei; Yongfu Deng; Zhenhao Lin; Chuanhui Xu; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2023)

Experimental and Numerical Investigations on Rock Breaking of TBM Disc Cutter Based on a Novel Platform with Rotational Cutting - Long-Chuan Deng; Fu-Bing Zhang; Xiao-Zhao Li; Chi Zhang; Yu-Kun Ji; Yun Wu (Rock Mechanics and Rock Engineering, 2023)

The GZnC1 variant from common wild rice influences grain Zn content - Jingjing Hou; Hao Chen; Kun Zhang; Wenjing Liu; Caihong Cao; Yini Ruan; Yanyan Deng; Yaxin Liu; Xuzhao Yuan; Chuanqing Sun; Yongcai Fu (Plant Molecular Biology, 2023)

Three-Dimensional Refined Modelling of Deep Structures by Using the Level Set Method: Application to the Zhaoping Detachment Fault, Jiaodong Peninsula, China - Jinli Wang; Xiancheng Mao; Cheng Peng; Jin Chen; Hao Deng; Zhankun Liu; Wensheng Wang; Zhengkai Fu; Chuntan Wang (Mathematical Geosciences, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Cover crop by irrigation and fertilization improves soil health and maize yield: Establishing a soil health index - Peng Li; Huijuan Zhang; Jianjun Deng; Libo Fu; Hua Chen; Chunkai Li; Li Xu; Jiaguo Jiao; Shixiang Zhang; Jidong Wang; Duo Ying; Huixin Li; et al. (Applied Soil Ecology, 2023)

Graph learning and denoising-based weighted sparse unmixing for hyperspectral images - Fu-Xin Song; Shi-Wen Deng (International Journal of Remote Sensing, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

The chloroplast GATA-motif of Mahonia bealei participates in alkaloid-mediated photosystem inhibition during dark to light transition - Jiaqi Chen; Tianfu Jiang; Jiajun Jiang; Linfang Deng; Yiting Liu; Zhuoheng Zhong; Hongwei Fu; Bingxian Yang; Lin Zhang (Journal of Plant Physiology, 2023)

Study on the quality characteristics of hot-dry noodles by microbial polysaccharides - Yixuan Liu; Xiaorong Liu; Liuyu Wan; Peng Xu; Xiaoyi Deng; Beibei Ding; Xuedong Wang; Yang Fu (Food Research International, 2023)

An ultrasensitive lateral flow immunoassay platform for foodborne biotoxins and pathogenic bacteria based on carbon-dots embedded mesoporous silicon nanoparticles fluorescent reporter probes - Yuhui Wang; Chen Deng; Sihua Qian; Hui Li; Pan Fu; Hualan Zhou; Jianping Zheng (Food Chemistry, 2023)

Effects of haloxyfop-p-methyl on the developmental toxicity, neurotoxicity, and immunotoxicity in zebrafish - Yi Liu; Jing Guo; Wenjin Liu; Fengjie Yang; Yunyun Deng; Yunlong Meng; Bo Cheng; Jianping Fu; June Zhang; Xinjun Liao; Lili Wei; Huiqiang Lu (Fish & Shellfish Immunology, 2023)

Supercooled sugar alcohols stabilized by alkali hydroxides for long-term room-temperature phase change solar-thermal energy storage - Xiaoxiang Li; Jingyi Zhang; Yizhe Liu; Yangzhe Xu; Kehang Cui; Zhenpeng Yao; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2023)

Effect of natural organic matter on Cr(VI) reduction by reduced nontronite - Liyan Deng; Fu Liu; Zecong Ding; Yuzhen Liang; Zhenqing Shi (Chemical Geology, 2023)

Catalytic hydrolysis of corncob for production of furfural and cellulose-rich solids: Product characterization and analysis - Bang Yao; Qinhao Kang; Jie Fu; Yang Liu; Wenya Ao; Long Wang; Zhihui Jiang; Tianhao Zhang; Yongmeng Song; Zeyu Deng; Asif Ali Siyal; Jianjun Dai (Biomass and Bioenergy, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

Effects of the probability of pulse-like ground motions on landslide susceptibility assessment in near-fault areas - Jing Liu; Hai-ying Fu; Ying-bin Zhang; Pei-yi Xu; Run-dan Hao; Hai-hong Yu; Yun-yong He; Hong-yan Deng; Lu Zheng (Journal of Mountain Science, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Hydrogeological Control on Coalbed Methane Geochemistry in CO2/N2-Enriched Secondary Microbial Gas Areas: A Case Study in the Eastern Section of the Southern Junggar Basin, NW China - Baoxin Zhang; Ze Deng; Xuehai Fu; Yibing Wang; Longjiang Fan; Junqiang Kang; Zhenzhi Wang; Yanyan Ge (Natural Resources Research, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

A comprehensive review on coupled processes and mechanisms of soil-vegetation-hydrology, and recent research advances - Zhongkai Li; Xiaoyan Li; Sha Zhou; Xiaofan Yang; Yongshuo Fu; Chiyuan Miao; Shuai Wang; Guanghui Zhang; Xiuchen Wu; Chao Yang; Yuanhong Deng (Science China Earth Sciences, 2022)

Increased expression of Myosin X contributes to the metastasis in patients with laryngeal squamous cell carcinoma - Gang Deng; Tie-Jun Fu; Cui-Ping Liu (Molecular Genetics and Genomics, 2022)
Laryngeal Squamous Cell Carcinoma (LSCC) is one of the most common malignancy in Head and neck cancer for which the mechanism underlying its metastasis is poorly understood. Myosin X, a molecular motor in cells has been demonstrated to play an important role in cell migration. However, whether Myosin X is involved in the metastasis of LSCC remains unclear. To investigate the expression of Myosin X and its implication in the metastasis of LSCC, we recruited 30 patients with LSCC and 6 patients with vocal cord polyp range from October 2016 to October 2018. Tissue samples were obtained during surgery and the expression of Myosin X, Cortactin, MMP2, MMP9, E-cadherin, and β-catenin in tissue samples were evaluated by RT-PCR, Western blot, immunohistochemistry or ELISA. Patients with LSCC were further followed-up 2 year after surgery for metastasis analysis. We found that the level of Myosin X, Cortactin, MMP2, and MMP9 was much higher in poorly differentiated LSCC compared to that in moderately and highly LSCC, as well as the control tissues. In contrast, the expression of epithelial-mesenchymal transition related marker, E-cadherin, and β-catenin, were much lower in poorly differentiated LSCC tissues compared to that in moderately and highly differentiated LSCC tissues, as well as the control tissues. Moreover, the expression of Myosin X was positively correlated with Cortactin, MMP2, and MMP9 levels. Increased expression of Myosin X in LSCC tissues was related to higher risk of metastasis. In conclusion, our findings showed that. Myosin X augments the expression of Cortactin, MMP2 and MMP9, which could upregulate the cell migration and the matrix degradation, and consequently reduce the expression of E-cadherin and β-catenin, thereby activating epithelial-mesenchymal transformation and promoting the metastasis of LSCC. Targeting Myosin X may have potential therapeutic effect in the metastasis of LSCC.

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Coupled Thermo–Mechanical Damage Evolution of Granite under Repeated Heating–Cooling Cycles and the Applications of Mohr–Coulomb and Drucker–Prager Models - Jian Yang; Li-Yun Fu; Fei Wang; Wubing Deng (Natural Resources Research, 2022)

The melanocortin-4 receptor (MC4R) gene in the gibel carp Carassius auratus gibelio: cloning, tissue distribution, and fasting effects - Yan Zhou; Yan Li; Luo Lei; Xingxing Deng; Yuting Duan; Suxing Fu; Jingsen Zhang; Dengyue Yuan; Chaowei Zhou; Wenping He (Aquaculture International, 2022)

Bearing Characteristics of Multi-Wing Pile Foundations under Lateral Loads in Dapeng Bay Silty Clay - Hao Wang; Dewei Fu; Tiantian Yan; Deng Pan; Weiwei Liu; Liqun Ma (Journal of Marine Science and Engineering, 2022)
This study provides a theoretical basis for reinforcement of the soil around multi-wing piles. Limit analysis was used to determine the ultimate lateral capacity (ULC) of three- and four-wing piles in Dapeng Bay silty clay. The effects of the pile–soil interaction coefficient α, wing width Bw, and lateral-load direction β on the ULC of the pile and the shear plastic zone range of the surrounding soil were analyzed. The normalized ULC of the three-wing pile decreased when the wing–diameter ratio increased. When Bw was 0.15 m and α was 0.4, the ULC of the four-wing pile was 19% higher than that of the three-wing pile. As β increased, the normalized ULC of the four-wing pile decreased, whereas that of the three-wing pile went through a minimum at 30°. The size of the soil shear plastic ring did not depend on α for either pile type; it increased around the three-wing (but not the four-wing) pile with changes in β. However, there was also a double plastic ring of broken soil around the four-wing pile. The four-wing pile had a more symmetrical influence on the soil around the pile than the three-wing pile.

Risk control effectiveness of phosphorus-containing passivators on Cd-contaminated agricultural soils to be strictly controlled - Chunfa Wu; JinLu Zhang; Yu Zhang; Shaopo Deng; Chong Wang; Zhaocong Fu (Journal of Soils and Sediments, 2022)

Long term high fat diet induces metabolic disorders and aggravates behavioral disorders and cognitive deficits in MAPT P301L transgenic mice - Jing Xiong; Isaac Deng; Sally Kelliny; Liying Lin; Larisa Bobrovskaya; Xin-Fu Zhou (Metabolic Brain Disease, 2022)

Effect of different washing solutions on soil enzyme activity and microbial community in agricultural soil severely contaminated with cadmium - Yu Zhang; Chunfa Wu; Shaopo Deng; Jinlu Zhang; Jinyu Hou; Chong Wang; Zhaocong Fu (Environmental Science and Pollution Research, 2022)

Multi-Omics Study on the Molecular Mechanisms of Tetraodon Nigroviridis Resistance to Exogenous Vibrio Parahaemolyticus Infection - Shoujia Jiang; Lijun Fu; Zijian Gao; Hengwei Deng; Yong Zhang; Xinxin You; Qiong Shi; Danqi Lu (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is an important marine pathogen that causes inflammation and even death in teleost fishes. It has brought significant economic losses to the aquaculture industry as well as high risks to the sustainable development of marine fisheries. In the present study, the fish Tetraodon nigroviridis and the bacterial pathogen Vibrio parahaemolyticus were used to explore the molecular mechanisms underlying the immune response of T. nigroviridis to V. parahaemolyticus exogenous infection. The microRNA (miRNA)–mRNA–protein omics and corresponding experimental validation, followed by comparative analysis, revealed several differentially expressed genes involved in various components of the immune system, including the following: complement system, chemokines, lysosomes, phagocytes, B-cell receptor signaling pathway, T-cell receptor signaling pathway, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway, and phospholipid metabolism, among others. Especially, the complements component 3 (C3) gene and protein expression levels were significantly higher after V. parahaemolyticus infection, and miRNAs targeting C3, including mir-6089-y, mir-460-y, and mir-1584-x, were significantly down-regulated. The gene and protein expression levels of complement 1 subunit qA (C1qA) were significantly down-regulated, while mir-203 targeting C1qA was significantly up-regulated. Overall, four complement genes (C1qA, IG, C3, and C5) , which are key genes in the classical pathway of complement system activation for inflammatory response, were identified. Evolutionary analysis suggested that T. nigroviridis, acquired an increased ability to recognize pathogens by evolving a more complex complement system than terrestrial vertebrates. In addition, quantitative real-time polymerase chain reaction showed high consistency with the obtained multi-omics results, indicating the reliability of the sequencing data generated in the present study. In summary, our findings can serve as a fundamental basis for further in-depth multi-omics studies on the inflammatory processes of aquatic pathogens hindering fish sustainable production.

Pairwise coarse registration of point clouds by traversing voxel-based 2-plane bases - Yongjian Fu; Zongchun Li; Feng Xiong; Hua He; Wenqi Wang; Yong Deng (International Journal of Remote Sensing, 2022)

Role of Hfq in glucose utilization, biofilm formation and quorum sensing system in Bacillus subtilis - Mengyao Dong; Xingtao Yang; Lijuan Liu; Ziyao Zhou; Lei Deng; Zhijun Zhong; Haifeng Liu; Xiaoping Ma; Hualin Fu; Suizhong Cao; Liuhong Shen; Guangneng Peng (Biotechnology Letters, 2022)

Soil types determine vegetation communities along a toposequence in a dolomite peak-cluster depression catchment - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (Plant and Soil, 2022)

Genome-wide SNP analysis reveals the selection signatures of two indigenous buffalo breeds in Sichuan - Wei Wang; Donghui Fang; Yi Shi; Fang He; Jia Gan; Maozhong Fu; Xiaodong Deng; Tao Zhang; Hongbing Shen; Shengchao Zhong; Yueda Aguo; Luxi Chen; et al. (Conservation Genetics Resources, 2022)
Sichuan Province spawned abundant of indigenous buffalo varieties, which probably harbor valuable gene resources beneficial to the genetic improvement of buffalo. However, limited genetic information was publicly available. To better understand their selection signatures between different populations, we performed a restriction site-associated DNA sequencing (RADseq) to explore genome-wide SNPs among two indigenous breeds of Sichuan buffaloes. As a result, a total of 2,110,077 high-quality SNPs were finally obtained. Population genetic analysis indicated a obviously genetic differentiation between two breeds. The detection of selective genes showed that 995 and 910 protein-coding genes underwent positive selection in Yibin buffalo (GYBS) and Dechang buffalo (XCS). Further functional analysis revealed distinctly discrepant selection in two breeds. Candidate genes that positively selected from Yibin buffaloes have mainly occurred in functions closely related to meat quality, complex living environment adaption capability, and disease resistance. While they were significantly enriched in cell proliferation and cell components in Dechang buffalo, indicating the selection pressure primarily derived from the requirement of organism growth and development speed during breed formation. Our dataset constitutes a promising reservoir of genome-wide SNP markers of Sichuan buffaloes and provides potentially traits selected in different local populations. Such comprehensive genetic resources offer an unprecedented opportunity for genetic association analysis of economically important traits and precision breeding programs in buffaloes.

Seeing Is Believing: Time-Lapse Macro-Imaging of Morphological Changes of Solid Dosages as a Teaching and Research Tool - Li Deng; Yao Fu (Pharmaceutical Research, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

The evolution of material stock research: From exploring to rising to hot studies - Chenling Fu; Yan Zhang; Tianjie Deng; Ichiro Daigo (Journal of Industrial Ecology, 2022)
Material stocks in buildings, infrastructure, and durable products play multiple roles in environmental and socioeconomic systems throughout their life cycle. After half a century of exploration, the study of material stocks has led to the development of a knowledge system. However, an overall picture of the evolution of knowledge in this field is lacking. With the aid of CiteSpace , a science mapping tool, we review 395 publications and find that the study of material stock experienced three obvious stages: initial exploration (1973–2005); rising period (2006–2016); and a hot period (2017–2020). The evolution of material stock research shows a clear objective‐oriented mode. As research objectives evolved from macroscopic observation to refined management of materials, the main research content changed from observational accounting to exploring the application, role, and service functions of material stocks, especially from the perspective of systematic metabolism under the complex background of social transformation. Accounting items shifted from an initial focus on metallic materials to a broader set of materials and product stocks, and from accounting of a single category to multi‐category accounting. The scale of research correspondingly shifted from the national and global scale to the urban and community scale which can serve refined management. These changes also led to in‐depth and detailed study of the role and function of stocks. In the future, scholars should continue to explore and apply microscale models, “whiten” the black box in large scale research; focus on recycling of urban minerals and electronic wastes. Mapping the transformation of raw materials into products by combining material properties and product functions is crucial to concretely implement a circular economy. Differentiation, specialization, combination of approaches, and sub‐categorical and sub‐regional coefficients will be the key to future refined, lean, and precise accounting.

Ribosomal ITS sequence-directed selection for endophytic Myrothecium strains antagonistic to Ralstonia solanacearum to control patchouli bacterial wilt - Wenguang Shi; Jiaqi Li; Huaxiong Yao; Jianbin Li; Meiqi Chen; Danting Chen; Yinghao Fu; Huarong Xie; Zujun Deng (BioControl, 2022)

Characteristic and mechanism of marine-continental transitional shale hydration: a case study on disaggregated shale in Guizhou Province, South China - Baoxin Zhang; Wuzhong Li; Yiming Yang; Xuehai Fu; Yulin Shen; Ze Deng (Arabian Journal of Geosciences, 2022)

Airborne black carbon variations during the COVID-19 lockdown in the Yangtze River Delta megacities suggest actions to curb global warming - Hao Li; Kan Huang; Qingyan Fu; Yanfen Lin; Jia Chen; Congrui Deng; Xudong Tian; Qian Tang; Qingchuan Song; Zhen Wei (Environmental Chemistry Letters, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Characteristics of fine particulate matter (PM2.5) at Jinsha Site Museum, Chengdu, China - Jialin Deng; Luman Jiang; Wenwen Miao; Junke Zhang; Guiming Dong; Ke Liu; Juncheng Chen; Tong Peng; Yao Fu; Yunpei Zhou; Xue Huang; Mengqian Hu; et al. (Environmental Science and Pollution Research, 2022)

Aurantii Fructus: a systematic review of ethnopharmacology, phytochemistry and pharmacology - Tianhui Gao; Maoyuan Jiang; Bin Deng; Zhen Zhang; Qiang Fu; Chaomei Fu (Phytochemistry Reviews, 2021)

Investigation of Adsorption–Desorption, Induced Strains and Permeability Evolution During N2–ECBM Recovery - Zhenzhi Wang; Xuehai Fu; Ze Deng; Jienan Pan (Natural Resources Research, 2021)

Changes in the Urban Surface Thermal Environment of a Chinese Coastal City Revealed by Downscaling MODIS LST with Random Forest Algorithm - Nuo Xu; Fan Deng; Bingqi Liu; Caixia Li; Hancong Fu; Huan Yang; Jiahua Zhang (Journal of Meteorological Research, 2021)

Two metabolites isolated from endophytic fungus Coniochaeta sp. F-8 in Ageratina adenophora exhibit antioxidative activity and cytotoxicity - Jie Fu; Liwen Hu; Zhen Shi; Wei Sun; Dong Yue; Ya Wang; Xiaoping Ma; Zhihua Ren; Zhicai Zuo; Guangneng Peng; Zhijun Zhong; Junliang Deng; et al. (Natural Product Research, 2021)

RNA-binding protein Hfq plays a vital role in cellulose decomposition throughout affecting cellulase gene expression - Xingtao Yang; Mengyao Dong; Ziyao Zhou; Lei Deng; Cao Deng; Haifeng Liu; Zhijun Zhong; Hualin Fu; Zhihua Ren; Yanchun Hu; Liuhong Shen; Yi Geng; et al. (Biotechnology Letters, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

A New Approach to Model Sporadic Alzheimer’s Disease by Intracerebroventricular Streptozotocin Injection in APP/PS1 Mice - Sally Kelliny; Liying Lin; Isaac Deng; Jing Xiong; Fiona Zhou; Mohammed Al-Hawwas; Larisa Bobrovskaya; Xin-Fu Zhou (Molecular Neurobiology, 2021)

Solubilization and separation of o-toluidine and tricyclazole in sodium dodecyl sulfate micelles in micellar enhanced ultrafiltration - Peng Wu; Yiqing Liu; Yongsheng Fu; Gaofeng Zhou; Jiewen Deng (Environmental Science and Pollution Research, 2021)

A New Perspective on Ameliorating Depression-Like Behaviors: Suppressing Neuroinflammation by Upregulating PGC-1α - Xinxin Fu; Jie Jiao; Tingting Qin; Jiayu Yu; Qiang Fu; Xueyang Deng; Shiping Ma; Zhanqiang Ma (Neurotoxicity Research, 2021)

Estimation of Rape-Cultivated Area Based on Decision Tree and Mixed Pixel Decomposition - Huan Yang; Fan Deng; Hancong Fu; Jiahua Zhang (Journal of the Indian Society of Remote Sensing, 2021)

Effects of Methane Saturation and Nitrogen Pressure on N2–Enhanced Coalbed Methane Desorption Strain Characteristics of Medium-Rank Coal - Zhenzhi Wang; Ze Deng; Xuehai Fu; Guofu Li; Jienan Pan; Ming Hao; He Zhou (Natural Resources Research, 2021)

Transcriptomic and metabolomic analyses of non-structural carbohydrates in red maple leaves - Xiaoyu Lu; Zhu Chen; Xinyi Deng; Mingyuan Gu; Zhiyong Zhu; Jie Ren; Songling Fu (Functional & Integrative Genomics, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Testosterone deficiency accelerates early stage atherosclerosis in miniature pigs fed a high-fat and high-cholesterol diet: urine 1H NMR metabolomics targeted analysis - Liqun Deng; Danting Fu; Liang Zhu; Junjie Huang; Yun Ling; Zhaowei Cai (Molecular and Cellular Biochemistry, 2021)

Experimentally Induced Sepsis Causes Extensive Hypomyelination in the Prefrontal Cortex and Hippocampus in Neonatal Rats - Peixian Huang; Xuan Chen; Xiaoli Hu; Qiuping Zhou; Lanfen Lin; Shuqi Jiang; Hui Fu; Yajie Xiong; Hongke Zeng; Ming Fang; Chunbo Chen; Yiyu Deng (NeuroMolecular Medicine, 2020)

Direct regeneration of haploid or doubled haploid plantlets in cucumber (Cucumis sativus L.) through ovary culture - Ying Deng; Bing Tang; Xia Zhou; Wenyuan Fu; Lian Tao; Lu Zhang; Jinfeng Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Efficient removal of antibiotic oxytetracycline from water using optimized montmorillonite-supported zero-valent iron nanocomposites - Mai Lien Tran; Si-Wei Deng; Chun-Chieh Fu; Ruey-Shin Juang (Environmental Science and Pollution Research, 2020)

Estimation of PM2.5 Mass Concentration from Visibility - Denghui Ji; Zhaoze Deng; Xiaoyu Sun; Liang Ran; Xiangao Xia; Disong Fu; Zijue Song; Pucai Wang; Yunfei Wu; Ping Tian; Mengyu Huang (Advances in Atmospheric Sciences, 2020)
Aerosols in the atmosphere not only degrade visibility, but are also detrimental to human health and transportation. In order to develop a method to estimate PM 2.5 mass concentration from the widely measured visibility, a field campaign was conducted in Southwest China in January 2019. Visibility, ambient relative humidity (RH), PM 2.5 mass concentrations and scattering coefficients of dry particles were measured. During the campaign, two pollution episodes, i.e., from 4–9 January and from 10–16 January, were encountered. Each of the two episodes could be divided into two periods. High aerosol hygroscopicity was found during the first period, when RH was higher than 80% at most of the time, and sometimes even approached 100%. The second period experienced a relatively dry but more polluted condition and aerosol hygroscopicity was lower than that during the first period. An empirical relationship between PM 2.5 mass concentration and visibility (ambient aerosol extinction) under different RH conditions could thus be established. Based on the empirical relationship, PM 2.5 mass concentration could be well estimated from visibility and RH. This method will be useful for remote sensing of PM 2.5 mass concentration.

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Contrasting effects of light, soil chemistry and phylogeny on leaf nutrient concentrations in cave-dwelling plants - Kundong Bai; Yigang Wei; Denan Zhang; Longfei Fu; Shihong Lv; Lili Deng (Plant and Soil, 2020)

Magma generation and sulfide saturation of Permian mafic-ultramafic intrusions from the western part of the Northern Tianshan in NW China: implications for Ni-Cu mineralization - Yu-Feng Deng; Feng Yuan; Peter Hollings; Xie-Yan Song; Taofa Zhou; Bin Fu; Steven Denyszyn; Bingbing Zhao (Mineralium Deposita, 2020)

Latest Middle Miocene fauna and flora from Kumkol Basin of northern Qinghai-Xizang Plateau and paleoenvironment - Qiang Li; Xinying Zhou; Xijun Ni; Bihong Fu; Tao Deng (Science China Earth Sciences, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Does pipelaying method affect the development of pipeline geohazards and maintenance cost? A case study of Zhongxian-Wuhan gas pipeline, China - Qinglu Deng; Min Fu; Xingwei Ren (Bulletin of Engineering Geology and the Environment, 2020)

Ureteral involvement by metastatic malignant disease - Jieping Hu; Jun Deng; Ju Guo; Bin Fu (Clinical & Experimental Metastasis, 2019)

Complete genome sequence of the novel phage vB_BthS-HD29phi infecting Bacillus thuringiensis - Yajuan Fu; Sangsang Deng; Leiqin liang; Yan Wu; Meiying Gao (Archives of Virology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Electron Probe Microanalysis of Monazite and Its Applications to U-Th-Pb Dating of Geological Samples - Wenbin Ning; Junpeng Wang; Deng Xiao; Fenfang Li; Bo Huang; Dong Fu (Journal of Earth Science, 2019)

Comparison of methods for extracting annual cycle with changing amplitude in climate series - Qimin Deng; Zuntao Fu (Climate Dynamics, 2019)

Influence of provenance and shade on biomass production and triterpenoid accumulation in Cyclocarya paliurus - Bo Deng; Shengzuo Fang; Xulan Shang; Xiangxiang Fu; Yan Li (Agroforestry Systems, 2019)

Meteorological conditions during a severe, prolonged regional heavy air pollution episode in eastern China from December 2016 to January 2017 - Xueliang Deng; Weihua Cao; Yanfeng Huo; Guanying Yang; Caixia Yu; Dongyan He; Weitao Deng; Wei Fu; Heming Ding; Jing Zhai; Long Cheng; Xuhui Zhao (Theoretical and Applied Climatology, 2019)

Integrative genomic analysis predicts novel functional enhancer-SNPs for bone mineral density - Chuan Qiu; Hui Shen; Xiaoying Fu; Chao Xu; Qing Tian; Hongwen Deng (Human Genetics, 2019)

Characteristics and significance of heterogeneity of sea-land transitional facies shale gas reservoir in North Guizhou, China - Ran Wang; Shuxun Sang; Jun Jin; Lingyun Zhao; Wei Gao; Wei Fu; Fulun Shi; Ende Deng (Geosciences Journal, 2019)

Ethical considerations of cellular immunotherapy for cancer - Sang-sang Ren; Jing-wen Deng; Meng Hong; Yan-li Ren; Hai-jing Fu; Yan-ning Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Full-length and defective enterovirus G genomes with distinct torovirus protease insertions are highly prevalent on a Chinese pig farm - Yan Wang; Wen Zhang; Zhijian Liu; Xingli Fu; Jiaqi Yuan; Jieji Zhao; Yuan Lin; Quan Shen; Xiaochun Wang; Xutao Deng; Eric Delwart; Tongling Shan; et al. (Archives of Virology, 2018)

miR-128-3p regulates 3T3-L1 adipogenesis and lipolysis by targeting Pparg and Sertad2 - Chen Chen; Yuan Deng; Xionggui Hu; Huibo Ren; Ji Zhu; Shengcai Fu; Julan Xie; Yinglin Peng (Journal of Physiology and Biochemistry, 2018)

Levo-tetrahydropalmatine Attenuates Neuron Apoptosis Induced by Cerebral Ischemia–Reperfusion Injury: Involvement of c-Abl Activation - Ruoxi Sun; Yichen Song; Shanshan Li; Zhanqiang Ma; Xueyang Deng; Qiang Fu; Rong Qu; Shiping Ma (Journal of Molecular Neuroscience, 2018)

Spatio-temporal simulation of the geopolitical environment system - Quansheng Ge; Dong Jiang; Feng Lu; Jingying Fu; Shaoqiang Wang; Xiangzheng Deng (Journal of Geographical Sciences, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

The impact of inter-annual variability of annual cycle on long-term persistence of surface air temperature in long historical records - Qimin Deng; Da Nian; Zuntao Fu (Climate Dynamics, 2018)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Effects of moso bamboo (Phyllostachys edulis) invasions on soil nitrogen cycles depend on invasion stage and warming - Zhenzhen Li; Ling Zhang; Bangliang Deng; Yuanqiu Liu; Fanqian Kong; Guoxian Huang; Qin Zou; Qian Liu; Xiaomin Guo; Yanqiu Fu; Dekui Niu; Evan Siemann (Environmental Science and Pollution Research, 2017)

Genome-wide identification and functional analysis of S-RNase involved in the self-incompatibility of citrus - Mei Liang; Wei Yang; Shiying Su; Lili Fu; Hualin Yi; Chuanwu Chen; Xiuxin Deng; Lijun Chai (Molecular Genetics and Genomics, 2017)

The integrated impacts of human activities and rising sea level on the saltwater intrusion in the east coast of the Yucatan Peninsula, Mexico - Yujun Deng; Caitlin Young; Xinyu Fu; Jie Song; Zhong-Ren Peng (Natural Hazards, 2017)

A pH-Sensitive Nanocarrier for Tumor Targeting - Ligang Chen; Chen Fu; Yajun Deng; Wei Wu; Ailing Fu (Pharmaceutical Research, 2016)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Synthesis and antimicrobial evaluation of 3-substituted-imine-6-hydroxy-benzofuran derivatives - Wan He; Buzhe Xu; Jian Bao; Xinxian Deng; Wenlu Liu; Yong Zhang; Faqin Jiang; Lei Fu (Medicinal Chemistry Research, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Mining-induced ground movement in tectonic stress metal mines: a case study - Kaizong Xia; Congxin Chen; Xiumin Liu; Hua Fu; Yucong Pan; Yangyang Deng (Bulletin of Engineering Geology and the Environment, 2016)

Impact of transduction towards the proliferation and migration as well as the transduction efficiency of human umbilical cord-derived late endothelial progenitor cells with nine recombinant adeno-associated virus serotypes - Zhaofei Wang; Qiang Fu; Jianguo Cao; Xiyun Deng; Yue Li; Qiaofeng Wang; Zhaofen Zheng (Biotechnology Letters, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

New material of Palaeocarya from the Oligocene of Ningming, Guangxi, South China - Jun-Ling Dong; Wen-Jia Wang; Peng Deng; Jin Wang; Fu-Jun Ma; Qiu-Jun Wang; Yi Yang; Bai-Nian Sun (PalZ, 2016)

Isolation and characterization of 13 polymorphic microsatellite loci for the fig wasp, Ceratosolen sp. (Hymenoptera: Agaonidae) - Lu Tan; Jun-Yin Deng; Rong-Hua Fu; Yan Chen (Applied Entomology and Zoology, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Re–Os and U–Pb geochronology of the Laochang Pb–Zn–Ag and concealed porphyry Mo mineralization along the Changning–Menglian suture, SW China: implications for ore genesis and porphyry Cu–Mo exploration - Xiao-Dong Deng; Jian-Wei Li; Xin-Fu Zhao; Hong-Qiang Wang; Liang Qi (Mineralium Deposita, 2016)

Bufavirus Protoparvovirus in feces of wild rats in China - Shixing Yang; Dawei Liu; Yan Wang; Fanyong Qu; Yilin He; Zixuan Sun; Quan Shen; Wang Li; Xingli Fu; Xutao Deng; Wen Zhang; Eric Delwart (Virus Genes, 2016)

Analysis of urbanization based on center-of-gravity movement and characteristics in Songhua River basin of China and its southern source sub-basin between 1990 and 2010 - Xiao Fu; Yuan Shen; Rencai Dong; Hongbing Deng; Gang Wu (Chinese Geographical Science, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

NMR-Based Metabolic Profiling Reveals Neurochemical Alterations in the Brain of Rats Treated with Sorafenib - Changman Du; Xue Shao; Ruiming Zhu; Yan Li; Qian Zhao; Dengqi Fu; Hui Gu; Jueying Kong; Li Luo; Hailei Long; Pengchi Deng; Huijuan Wang; et al. (Neurotoxicity Research, 2015)

Production of sweet orange somaclones tolerant to citrus canker disease by in vitro mutagenesis with EMS - Hongjuan Ge; Yi Li; Hongyan Fu; Guiyou Long; Li Luo; Ronghua Li; Ziniu Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Residue behavior and risk assessment of mixed formulation of imidacloprid and chlorfenapyr in chieh-qua under field conditions - Jian Xiang Huang; Cong Yun Liu; Da Hai Lu; Jia Jia Chen; Yi Cai Deng; Fu Hua Wang (Environmental Monitoring and Assessment, 2015)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Sedimentary successions and the onset of the Neoproterozoic Jiangnan sub-basin in the Nanhua rift, South China - Jian Wang; Xiaolin Zhou; Qi Deng; Xiugen Fu; Taizhong Duan; Xiumei Guo (International Journal of Earth Sciences, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Impact of long-term zero-flow and ecological water conveyance on the radial increment of Populus euphratica in the lower reaches of the Tarim River, Xinjiang, China - Xiaoya Deng; Hailiang Xu; Mao Ye; Bailian Li; Jinyi Fu; Zhifeng Yang (Regional Environmental Change, 2015)

An anther development F-box (ADF) protein regulated by tapetum degeneration retardation (TDR) controls rice anther development - Li Li; Yixing Li; Shufeng Song; Huafeng Deng; Na Li; Xiqin Fu; Guanghui Chen; Longping Yuan (Planta, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Chicken 15-kDa Selenoprotein Plays Important Antioxidative Function in Splenocytes - Huijie Sun; Tingquan Deng; Jiaxing Fu (Biological Trace Element Research, 2014)

Ion dynamics associated with substorm dipolarization fronts - Song Fu; Maha Ashour-Abdalla; XiaoHua Deng; Mostafa El-Alaoui; Meng Zhou; Robert L. Richard; Raymond J. Walker; ZhiGang Yuan (Science China Earth Sciences, 2014)

Effect of photosynthetic bacteria on water quality and microbiota in grass carp culture - Xiaoping Zhang; Miaoan Shu; Yibing Wang; Luoqin Fu; Weifen Li; Bin Deng; Quan Liang; Wenying Shen (World Journal of Microbiology and Biotechnology, 2014)

Neuroprotective role of BNIP3 under oxidative stress through autophagy in neuroblastoma cells - M. Umer Farooq Awan; Murtaza Hasan; Javed Iqbal; Runhong Lei; Wang Fu Lee; Ma Hong; Hong Qing; Yulin Deng (Molecular Biology Reports, 2014)

The population genomic landscape of human genetic structure, admixture history and local adaptation in Peninsular Malaysia - Lian Deng; Boon Peng Hoh; Dongsheng Lu; Ruiqing Fu; Maude E. Phipps; Shilin Li; Ab Rajab Nur-Shafawati; Wan Isa Hatin; Endom Ismail; Siti Shuhada Mokhtar; Li Jin; Bin Alwi Zilfalil; et al. (Human Genetics, 2014)

Muscular tubes of urethra engineered from adipose-derived stem cells and polyglycolic acid mesh in a bioreactor - Ying Wang; Qiang Fu; Ren-Yan Zhao; Chen-Liang Deng (Biotechnology Letters, 2014)

Post-transcriptional gene regulation by RNA-binding proteins in vascular endothelial dysfunction - HongBo Xin; KeYu Deng; MinGui Fu (Science China Life Sciences, 2014)

Tree bark as a passive air sampler to indicate atmospheric polybrominated diphenyl ethers (PBDEs) in southeastern China - Xiaoxu Fu; Junxia Wang; Xiaoyu Zhou; Jingjing Deng; Yangcheng Liu; Wei Zhang; Lili Liu; Liang Dong; Kuangfei Lin (Environmental Science and Pollution Research, 2014)

Hazardous substances in indoor dust emitted from waste TV recycling facility - Jingjing Deng; Jie Guo; Xiaoyu Zhou; Peng Zhou; Xiaoxu Fu; Wei Zhang; Kuangfei Lin (Environmental Science and Pollution Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Isolation, Expression, and Characterization of Blue Light Receptor AUREOCHROME Gene From Saccharina japonica (Laminariales, Phaeophyceae) - Yunyan Deng; Jianting Yao; Gang Fu; Hui Guo; Delin Duan (Marine Biotechnology, 2014)

Involvement of the nuclear factor-κB pathway in the adhesion of neutrophils to renal tubular cells after injury induced by neonatal postasphyxial serum - Tao Xiong; Wenbin Dong; Hui Fu; Qingping Li; Cunliang Deng; Xiaoping Lei; Lin Guo (Molecular and Cellular Biochemistry, 2014)

Vegetation cover variation in the Qilian Mountains and its response to climate change in 2000–2011 - Shao-fu Deng; Tai-bao Yang; Biao Zeng; Xi-fen Zhu; Hao-jie Xu (Journal of Mountain Science, 2013)

Effects of stocking density, diet, and water exchange on growth and survival of pearl oyster Pinctada maxima larvae - Yuewen Deng; Shao Fu; Feilong Liang; Shaohe Xie (Aquaculture International, 2013)

Comments on ‘Influences of the Bermuda High and atmospheric moistening on changes in summer rainfall in the Atlanta, Georgia region, USA ’ - Wenhong Li; Laifang Li; Rong Fu; Yi Deng; Hui Wang (International Journal of Climatology, 2013)
In a recent article, Diem (2012) examined the impact of the North Atlantic Subtropical High ( NASH ) and atmospheric moistening on summer rainfall variability in the Atlanta, Georgia region. In his paper, he indicated that the results concerning the variability of the NASH western ridge discussed in Li et al . (2011) are incorrect. We present new evidence here to show that the comments by Diem (2012) are unjustified; the main conclusions in Li et al . (2011) were drawn according to the data over a 60‐year (1948–2007) and 45‐year (1958–2002) periods of NCEP / NCAR and ERA ‐40 reanalysis, whereas conclusions of Diem (2011) were based upon the trend analysis of a similar but different index of the NASH using sub‐periods of 1948–2009 (since late 1970s). The comment emphases the importance of climate dynamics to study precipitation variability over the Southeastern US and further strengthens the conclusions originally put forth in Li et al . (2011): over the last 60 years (1948–2007), the NASH has shown a significant trend of westward movement, and the meridional movement of the NASH western‐ridge (i.e. its latitudinal change) has enhanced in the recent three decades.

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Bacillus subtilis SC02 supplementation causes alterations of the microbial diversity in grass carp water - Xiaoping Zhang; Luoqin Fu; Bin Deng; Quan Liang; Jiajia Zheng; Jiandong Sun; Haiyan Zhu; Lisha Peng; Yibing Wang; Shen Wenying; Weifen Li (World Journal of Microbiology and Biotechnology, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

Polymorphic microsatellite markers in the guava fruit fly, Bactrocera correcta (Diptera: Tephritidae) - Nopparat Buahom; Yu Du; Yi Wu; Yuliang Deng; Xiaolong Jiang; Wei Fu; Zhihong Li (Applied Entomology and Zoology, 2013)

A new flavanocoumarin from the root of Flemingia philippinensis - Manqin Fu; Dun Deng; Riming Huang; Nenling Zhang; Zhiwei Su; Samuel X. Qiu (Natural Product Research, 2013)

Erratum to: Euryhalocaulis caribicus gen. nov., sp. nov., a New Member of the Family Hyphomonadaceae Isolated from the Caribbean Sea - Wenchao Deng; Yao Zhang; Xiabing Xie; Zihao Zhao; Yingnan Fu (Current Microbiology, 2013)

Euryhalocaulis caribicus gen. nov., sp. nov., a New Members of the Family Hyphomonadaceae Isolated from the Caribbean Sea - Wenchao Deng; Yao Zhang; Xiabing Xie; Zihao Zhao; Yingnan Fu (Current Microbiology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Induction of humoral and cellular immune responses against hepatitis C virus by vaccination with replicon particles derived from Sindbis-like virus XJ-160 - Wuyang Zhu; Juanjuan Fu; Jian Lu; Yao Deng; Huanqin Wang; Yan Wei; Lingling Deng; Wenjie Tan; Guodong Liang (Archives of Virology, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

The reduction in zinc concentration of wheat grain upon increased phosphorus-fertilization and its mitigation by foliar zinc application - Yue-Qiang Zhang; Yan Deng; Ri-Yuan Chen; Zhen-Ling Cui; Xin-Ping Chen; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Effects of Bacillus preparations on immunity and antioxidant activities in grass carp (Ctenopharyngodon idellus) - Li Weifen; Zhang Xiaoping; Song Wenhui; Deng Bin; Liang Quan; Fu Luoqin; Zheng Jiajia; Wang yue; Yu Dongyou (Fish Physiology and Biochemistry, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

The Reanalysis of Currents and Throughflow Volume Transport in the Taiwan Strait - Ting Yu; Zengan Deng; Guijun Han; Xinrong Wu; Hongli Fu; Kejian Wu (Marine Geodesy, 2012)

Arsenic, Antimony, and Bismuth Uptake and Accumulation by Plants in an Old Antimony Mine, China - Chaoyang Wei; Qiujing Deng; Fengchang Wu; Ziyou Fu; Libin Xu (Biological Trace Element Research, 2011)

A novel direct equipartition ray design (EquRay) procedure for toxicity interaction between ionic liquid and dichlorvos - Rong-Ni Dou; Shu-Shen Liu; Ling-Yun Mo; Hai-Ling Liu; Fu-Cai Deng (Environmental Science and Pollution Research, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Growth performance and physiological parameters of the second generation selected and control groups of Pinctada martensii - Yuewen Deng; Ziniu Yu; Xiaodong Du; Qingheng Wang; Shao Fu (Acta Oceanologica Sinica, 2011)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Characterization of microsatellite DNA markers in the Emei moustache toads (Leptobrachium boringii) - Ke Bi; Duncan Deng; M. Kathrine A. Crosby; Jinzhong Fu (Conservation Genetics, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Distinct expression patterns of hedgehog ligands between cultured and primary colorectal cancers are associated with aberrant methylation of their promoters - Xiangsheng Fu; Hong Deng; Luping Zhao; Jing Li; Yongbai Zhou; Yali Zhang (Molecular and Cellular Biochemistry, 2010)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

A High Polymorphism Level in Rhinopithecus roxellana - Deng Pan; Hong-Xing Hu; Shi-Jie Meng; Zheng-Ming Men; Yun-Xin Fu; Ya-Ping Zhang (International Journal of Primatology, 2009)

Cloning and Characterization of a Stearoyl–Acyl Carrier Protein Desaturase Gene from Cinnamomum longepaniculatum - Tong Luo; Wu Yuan Deng; Jin Zeng; Fu Li Zhang (Plant Molecular Biology Reporter, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Origin of the Tongshankou porphyry–skarn Cu–Mo deposit, eastern Yangtze craton, Eastern China: geochronological, geochemical, and Sr–Nd–Hf isotopic constraints - Jian-Wei Li; Xin-Fu Zhao; Mei-Fu Zhou; Paulo Vasconcelos; Chang-Qian Ma; Xiao-Dong Deng; Zorano Sérgio de Souza; Yong-Xin Zhao; Gang Wu (Mineralium Deposita, 2008)

Mitochondrial Control Region and Population Genetic Patterns of Nycticebus bengalensis and N. pygmaeus - Deng Pan; Jing-Hua Chen; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Xiangyu Jinggong; Vu Ngoc Thanh; Oliver Ryder; Leona Chemnick; Hong-Wei Zhang; et al. (International Journal of Primatology, 2007)

Production and molecular characterization of potential seedless cybrid plants between pollen sterile Satsuma mandarin and two seedy Citrus cultivars - Xiao-Dong Cai; Jing Fu; Xiu-Xin Deng; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

Molecular Phylogeny of Nycticebus Inferred from Mitochondrial Genes - Jing-Hua Chen; Deng Pan; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Vu Ngoc Thanh; Oliver Ryder; Hong-Wei Zhang; Yun-xin Fu; Ya-ping Zhang (International Journal of Primatology, 2006)

GISH, AFLP and PCR-RFLP analysis of an intergeneric somatic hybrid combining Goutou sour orange and Poncirus trifoliata - C. H. Fu; C. L. Chen; W. W. Guo; X. X. Deng (Plant Cell Reports, 2004)

Isolating high-quality RNA from mangroves without liquid nitrogen - Xinhui Fu; Shulin Deng; Guohua Su; Qinglu Zeng; Suhua Shi (Plant Molecular Biology Reporter, 2004)

Regeneration of citrus sinensis (+) clausena lansium intergeneric triploid and tetraploid somatic hybrids and their identification by molecular markers - C. H. Fu; W. W. Guo; J. H. Liu; X. X. Deng (In Vitro Cellular & Developmental Biology - Plant, 2003)

BDNF is involved in sympathetic sprouting in the dorsal root ganglia following peripheral nerve injury in rats - Yan-Shen Deng; Jin-Hua Zhong; Xin-Fu Zhou (Neurotoxicity Research, 1999)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)

Inferring the major genomic mode of dominance and overdominance - Hong-Wen Deng; Yun-Xin Fu; Michael Lynch (Genetica, 1998)